Adhesive sheet

The adhesive sheet with heat-expandable microspheres balances initial low adhesiveness with strong bonding by heating, enhancing peelability for reprocessing and recycling.

CN112457796BInactive Publication Date: 2025-01-03NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010903131.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-09-01
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing adhesive sheets struggle to balance initial low adhesiveness for easy application and reprocessing with strong adhesiveness for bonding, and lack easy peelability for removal and recycling.

Method used

An adhesive sheet with a heat-expandable microsphere-containing adhesive layer that increases adhesive strength upon heating and reduces adhesiveness by expanding the microspheres, allowing for easy peelability.

Benefits of technology

The adhesive sheet achieves a significant increase in adhesive force after heating, enabling strong bonding while maintaining easy peelability for reprocessing and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112457796B_ABST
    Figure CN112457796B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet including an adhesive layer. The adhesive layer includes a polymer A as a base polymer and heat-expandable microspheres having an expansion starting temperature T1. The adhesive sheet is bonded to a stainless steel plate and heated at a temperature 20°C lower than the expansion starting temperature T1 for 5 minutes, and the adhesive force N2 measured at 23°C is 3.0 times or more of the adhesive force N1 measured after being bonded to the stainless steel plate and kept at 23°C for 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet. Background Art

[0002] Generally, adhesives (also called pressure-sensitive adhesives, the same below) are in a soft solid (viscoelastic) state in a temperature range near room temperature, and have the property of being easily bonded to an adherend by pressure. By utilizing this property, adhesives are widely used in various fields in the form of adhesive sheets with a substrate having an adhesive layer on a substrate or in the form of substrate-free adhesive sheets without a substrate.

[0003] Various properties are required of adhesives according to their uses. Among these properties, there is a tendency that if one property is improved, another property will be reduced, etc., which makes it difficult to take both into account at a high level. As an example of properties that are in a relationship that is difficult to take into account, the adhesion to the adherend and the reprocessability can be cited. The above-mentioned reprocessing means: when, for example, a sticking defect (position offset, wrinkles, occurrence of bubbles, inclusion of foreign matter, etc.) occurs when the adhesive sheet is pasted to the adherend, or when a bad condition is observed on the adherend after pasting the adhesive sheet, the adhesive sheet is peeled off from the adherend and pasted again. In response to this requirement, Patent Document 1 proposes an adhesive sheet that shows low adhesion in the initial stage of pasting to the adherend, and can subsequently significantly increase the adhesion.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6355874 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] According to the adhesive sheet described in Patent Document 1, by performing the steps of positioning and inspection before the adhesive strength increases, the good re-adhesiveness (reprocessability) is exhibited in the step, and the member can be reused. Moreover, after the adhesive strength is increased by heating, etc., the strong adhesiveness can be exhibited. On the other hand, the adhesive sheet whose adhesive strength is temporarily increased is easy to peel off again, but Patent Document 1 does not consider this. Improving the peelability of the adhesive sheet is beneficial in the case of repairing, recycling, and discarding the member to which the adhesive sheet is attached.

[0009] Therefore, an object of the present invention is to provide a pressure-sensitive adhesive sheet which exhibits low adhesiveness in the initial stage of being attached to an adherend, whose adhesive strength can be greatly increased by heating, and which has a function of being easily removable.

[0010] Solutions for solving problems

[0011] According to the specification, an adhesive sheet including an adhesive layer is provided. The aforementioned adhesive layer includes a polymer A as a base polymer and heat-expandable microspheres having an expansion starting temperature T1. The adhesive sheet is bonded to a stainless steel (SUS) plate and heated at a temperature 20°C lower than the aforementioned expansion starting temperature T1 for 5 minutes. The adhesive force N2 (hereinafter also referred to as "adhesive force after heating") measured at 23°C is 3.0 times or more of the adhesive force N1 (hereinafter also referred to as "initial adhesive force") measured after being bonded to a SUS plate and kept at 23°C for 30 minutes.

[0012] The adhesive sheet of this formation is large due to the ratio (hereinafter also referred to as "adhesive force rise ratio") of adhesive force (N2) after heating relative to initial adhesive force (N1), therefore, adhesive force can be greatly increased without expanding the heat-expandable microspheres compounded into the adhesive layer. In addition, by being heated to the temperature above the expansion starting temperature T1, the above-mentioned heat-expandable microspheres can be expanded and adhesive force can be reduced, and the peelability of the adhesive sheet for peeling off from the adherend can be improved.

[0013] The storage modulus G' of the polymer A at the expansion starting temperature T1 (hereinafter also referred to as "storage modulus G'(T1)") is preferably about 1×10 4 Pa~1×10 6 The PSA sheet having a PSA layer containing the polymer A as a base polymer has good adhesion to an adherend when the heat-expandable microspheres are not expanded, and easily exhibits releasability achieved by expanding the heat-expandable microspheres.

[0014] The glass transition temperature Tg of the polymer A is calculated based on the composition of the monomer components constituting the polymer A using the Fox equation. A It is preferably -65°C or higher and lower than 0°C. The PSA sheet having a PSA layer containing the polymer A as a base polymer has good adhesion to the adherend surface when the heat-expandable microspheres are not expanded, and easily exhibits releasability achieved by expanding the heat-expandable microspheres.

[0015] The content of the aforementioned heat-expandable microsphere in the aforementioned adhesive layer can be set to, for example, more than 10 weight parts and the scope below 200 weight parts relative to aforementioned polymer A 100 weight parts.According to the adhesive sheet with the adhesive layer of this composition, the strong adhesiveness after the adhesive force rises and the good peelability realized by expanding the heat-expandable microsphere can be suitably taken into account.

[0016] In some embodiments of the PSA sheet disclosed herein, the PSA layer may further include a polymer B, which is a copolymer of a monomer having a polyorganosiloxane skeleton and a (meth)acrylic monomer. By using polymer B, a PSA sheet having an adhesion increase ratio of 3.0 or more can be preferably realized.

[0017] The glass transition temperature Tg of the polymer B calculated based on the composition of the (meth)acrylic monomer and using the Fox equation is: B (hereinafter sometimes referred to as "Tg B ”) is preferably 30°C or higher and 120°C or lower. The adhesive sheet disclosed herein can be used with a Tg B This can be suitably achieved with polymer B within the above range.

[0018] In some embodiments, as the polymer B, the above-mentioned glass transition temperature Tg B The polymer has a Tg lower than the expansion starting temperature T1 by 20°C or more. B The polymer B can suitably realize a PSA sheet having high adhesive strength after heating and good releasability due to the expansion of the heat-expandable microspheres.

[0019] In some embodiments, the content of the polymer B in the adhesive layer can be set to, for example, 0.5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the polymer A. The content within the above range can appropriately balance the initial low adhesiveness and the strong adhesiveness after the adhesive force increases.

[0020] The adhesive sheet disclosed herein can be implemented in a form having a supporting substrate having a first surface and a second surface, and the adhesive layer is laminated on at least the first surface of the supporting substrate, that is, in the form of an adhesive sheet with a substrate. Such an adhesive sheet with a substrate can be formed into an adhesive sheet with good handling and processability.

[0021] Can be directly laminated with above-mentioned adhesive layer on the first side of above-mentioned supporting substrate, also can be laminated across other layers (middle layer).In a preferred version, between the aforementioned first face of aforementioned supporting substrate and the aforementioned adhesive layer, be configured with elastic middle layer.Thus, can effectively bring into play the adhesive force reduction effect realized by the expansion of the heat-expandable microsphere comprised by adhesive layer to adherend, and suitably maintain the form that is laminated with this adhesive layer across elastic middle layer on supporting substrate.

[0022] It should be noted that solutions obtained by appropriately combining the above-mentioned elements are also included in the scope of the invention sought for patent protection using this patent application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.

[0024] Figure 2 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0025] Figure 3 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0026] Description of Reference Numerals

[0027] 1, 2, 3 adhesive sheet

[0028] 10 Supporting substrate

[0029] 10A Side 1

[0030] 10B Side 2

[0031] 21 Adhesive layer (first adhesive layer)

[0032] 21A Adhesive surface (first adhesive surface)

[0033] 21B Adhesive surface (second adhesive surface)

[0034] 22 Adhesive layer (second adhesive layer)

[0035] 22A Adhesive surface (second adhesive surface)

[0036] 31, 32 Release liner

[0037] 50 Elastic middle layer

[0038] 100, 200, 300 Adhesive sheet with release liner (adhesive product) DETAILED DESCRIPTION

[0039] The following describes a suitable embodiment of the present invention. Matters other than those specifically mentioned in this specification and matters necessary for implementing the present invention can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0040] It should be noted that, in the following drawings, the same symbols are sometimes used to mark the components / parts that play the same role and explain them, and repeated explanations are sometimes omitted or simplified. In addition, the embodiments described in the drawings are schematically illustrated to clearly explain the present invention and do not necessarily accurately represent the size and scale of the actual product provided.

[0041] In addition, the term "acrylic polymer" in this specification refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer in the polymer structure, and typically refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer in a ratio of more than 50% by weight. In addition, a (meth)acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, "(meth)acryloyl" means a meaning including acryloyl and methacryloyl. Therefore, the concept of the so-called (meth)acrylic monomer here can include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, the term "(meth)acrylic acid" in this specification means a meaning including acrylic acid and methacrylic acid, and the term "(meth)acrylate" means a meaning including acrylate and methacrylate.

[0042] <Structural Example of Adhesive Sheet>

[0043] The adhesive sheet disclosed herein comprises an adhesive layer. The adhesive sheet disclosed herein may be in the form of an adhesive sheet with a substrate in which the adhesive layer is laminated on one side or both sides of a supporting substrate, or in the form of an adhesive sheet without a supporting substrate. Hereinafter, the supporting substrate may also be referred to as a "substrate".

[0044] The structure of the pressure-sensitive adhesive sheet according to one embodiment is schematically shown in Figure 1 The adhesive sheet 1 is formed in the form of a single-sided adhesive sheet with a substrate, and the single-sided adhesive sheet with a substrate includes a sheet-like supporting substrate 10 having a first surface 10A and a second surface 10B, and an adhesive layer 21 provided on the first surface 10A side. Figure 1 In the illustrated configuration, an elastic intermediate layer 50 is disposed between the first surface 10A of the supporting substrate 10 and the adhesive layer 21. That is, the adhesive layer 21 is laminated on the first surface 10A of the supporting substrate 10 via the elastic intermediate layer 50, and is preferably fixed. The elastic intermediate layer 50 is an arbitrary component and can be omitted. For example, the adhesive layer 21 can be directly laminated on the first surface 10A side of the supporting substrate 10, and is preferably fixed.

[0045] The adhesive sheet 1 is used by attaching the adhesive layer 21 to an adherend. Figure 1As shown, the adhesive sheet 1 before use (i.e. before being pasted on the adherend) can be a constituent element of the adhesive sheet 100 with a release liner in which the surface (adhesive surface) 21A of the adhesive layer 21 is in contact with the release liner 31 which becomes the releasable surface (release surface) on at least one side opposite to the adhesive layer 21. As the release liner 31, it is preferred to use a release liner which is constituted in a manner such as by arranging a release layer on one side of a sheet-like substrate (liner substrate) using a release treatment agent so that the single side becomes a release surface. Alternatively, it can be a form (roll form) in which the release liner 31 is omitted, the support substrate 10 whose second side 10B becomes the release surface is used, and the adhesive sheet 1 is wound so that the adhesive surface 21A is in contact with the second side 10B of the support substrate 10. When the adhesive sheet 1 is pasted on the adherend, the release liner 31 or the second side 10B of the support substrate 10 is peeled off from the adhesive surface 21A, and the exposed adhesive surface 21A is pressed against the adherend.

[0046] The structure of the adhesive sheet according to another embodiment is schematically shown in Figure 2 The adhesive sheet 2 is formed in the form of a double-sided adhesive sheet with a substrate, and the double-sided adhesive sheet with a substrate comprises a sheet-shaped supporting substrate 10 having a first surface 10A and a second surface 10B, an adhesive layer 21 provided on the first surface 10A side, and an adhesive layer 22 provided on the second surface 10B side. Figure 2 In the structure shown, an adhesive layer (first adhesive layer) 21 is directly laminated on the first surface 10A of the supporting substrate 10, and an adhesive layer (second adhesive layer) 22 is directly laminated on the second surface 10B of the supporting substrate 10, preferably fixed. Figure 2 In the structure shown in the figure, one or both of the space between the first surface 10A of the supporting substrate 10 and the adhesive layer 21 and the space between the second surface 10B of the supporting substrate 10 and the adhesive layer 22 may be connected with Figure 1 An elastic intermediate layer is also provided.

[0047] The adhesive sheet 2 is used by attaching the adhesive layers 21 and 22 to different locations on the adherend. The locations where the adhesive layers 21 and 22 are attached to the adherend may be locations of different components or different locations within a single component. Figure 2As shown in the figure, the adhesive sheet 2 before use can be a component of an adhesive sheet 200 with a release liner in which the surface (first adhesive surface) 21A of the adhesive layer 21 and the surface (second adhesive surface) 22A of the adhesive layer 22 are in contact with release liners 31 and 32, which are release surfaces on at least one side opposite to the adhesive layers 21 and 22. As the release liners 31 and 32, it is preferable to use a release liner that is formed in a manner such that the single side becomes a release surface by providing a release layer on one side of a sheet-like substrate (liner substrate) using a release treatment agent. Alternatively, by omitting the release liner 32, using a release liner 31 whose two sides become release surfaces, overlapping it with the adhesive sheet 2 and winding it into a spiral shape, it is possible to form an adhesive sheet with a release liner in a form (roll form) in which the second adhesive surface 22A is in contact with the back side of the release liner 31.

[0048] The structure of the adhesive sheet according to another embodiment is schematically shown in Figure 3 The adhesive sheet 3 is formed in the form of a double-sided adhesive sheet without a substrate formed by an adhesive layer 21. The adhesive sheet 3 is used by attaching a first adhesive surface 21A formed by one surface (first surface) of the adhesive layer 21 and a second adhesive surface 21B formed by the other surface (second surface) of the adhesive layer 21 to different parts of the adherend. Figure 3 As shown in the figure, the adhesive sheet 3 before use may be a component of an adhesive sheet 300 with a release liner in which the first adhesive surface 21A and the second adhesive surface 21B are in contact with release liners 31 and 32, which are release surfaces respectively on at least one side opposite to the adhesive layer 21. Alternatively, by omitting the release liner 32 and using a release liner 31 whose both sides are release surfaces, overlapping the release liner 3 with the adhesive sheet 3 and winding it into a spiral shape, an adhesive sheet with a release liner in which the second adhesive surface 21B is in contact with the back side of the release liner 31 (rolled form) may be formed.

[0049] The adhesive sheet disclosed herein may include one or more intermediate layers other than the elastic intermediate layer (hereinafter also referred to as "other intermediate layers") such as a primer layer, an adhesive layer, and an antistatic layer between the supporting substrate and the adhesive layer as required. When the adhesive sheet having the elastic intermediate layer between the supporting substrate and the adhesive layer further has the above-mentioned other intermediate layer, the above-mentioned other intermediate layer may be arranged between the supporting substrate and the elastic intermediate layer, between the elastic intermediate layer and the adhesive layer, or on both.

[0050] It should be noted that the concept of the adhesive sheet mentioned here may include adhesive sheets called adhesive tapes, adhesive films, adhesive labels, etc. The adhesive sheet may be in a roll form or a single sheet form, or may be cut or punched into a suitable shape according to the purpose and usage. The adhesive layer in the technology disclosed herein is typically formed continuously, but is not limited to this, and may also be formed into a regular or random pattern such as dots or strips.

[0051] <Characteristics of Adhesive Sheet>

[0052] (Adhesion strength increase ratio)

[0053] The adhesive force increase ratio of the adhesive sheet disclosed herein, which is defined in the form of the ratio of the adhesive force (N2) [N / 20mm] after heating to the initial adhesive force (N1) [N / 20mm] (i.e., N2 / N1), is preferably 3.0 or more. The adhesive sheet with a large adhesive force increase ratio is heated for a relatively short time at a temperature sufficiently lower than the expansion starting temperature T1 of the expandable microsphere (e.g., a temperature 20°C lower than the expansion starting temperature T1), so that the initial adhesive force can be greatly increased. Therefore, according to the adhesive sheet with a large adhesive force increase ratio, it is possible to suitably take into account the initial low adhesiveness and the strong adhesiveness during use. In addition, since the adhesive sheet after the adhesive force increase contains unexpanded heat-expandable microspheres, it is possible to improve the peelability of the adhesive sheet whose adhesive force temporarily increases by expanding it at any time.

[0054] From the viewpoint of taking into account both the initial low adhesiveness and the strong adhesiveness during use at a higher level, in some schemes, the adhesive force increase ratio is preferably more than 4.0, more preferably more than 5.0. In some schemes, the adhesive force increase ratio can be more than 6.0, can be more than 7.5, can be more than 10, can be more than 15, can be more than 18. The upper limit of the adhesive force increase ratio is not particularly limited, and from the viewpoint of easily and appropriately showing the peelability achieved by the expansion of the heat-expandable microspheres, for example, it can be less than 150, can be less than 100, can be less than 80, can be less than 50, can be less than 40, can be less than 30. The adhesive sheet disclosed herein can also be suitably implemented in the scheme where the adhesive force increase ratio is less than 20, less than 14 or less than 9.

[0055] (Initial Adhesion)

[0056] The initial adhesive force of the adhesive sheet disclosed herein is not particularly limited. The initial adhesive force can be set in a manner that gives play to the desired reprocessability according to the purpose and method of use of the adhesive sheet. In some schemes, the initial adhesive force can be, for example, less than 2.5N / 20mm, and it is suitable to be generally less than 2.3N / 20mm, and it can be less than 2.0N / 20mm, and it can be less than 1.5N / 20mm, and it can be less than 1.0N / 20mm. The lower limit of the initial adhesive force is not particularly limited, and it can be, for example, more than 0.001N / 20mm. From the viewpoint of the workability of being pasted on the adherend, preventing the positional deviation before the adhesive force rises, etc., the initial adhesive force is generally more than 0.01N / 20mm, and it is suitable, and from the viewpoint of the strong adhesiveness after the adhesive force rises that is easy to take into account, it can be, for example, more than 0.1N / 20mm. In some embodiments, the initial adhesion may be, for example, 0.3 N / 20 mm or more, 0.5 N / 20 mm or more, 0.8 N / 20 mm or more, or 1.2 N / 20 mm or more.

[0057] (Adhesion after heating)

[0058] For the adhesive sheet disclosed herein, the adhesive force after heating is not particularly limited, and can be set according to the purpose and method of use of the adhesive sheet. From the viewpoint of bonding reliability, in some schemes, the adhesive force after heating can be, for example, 2.5N / 20mm or more, usually preferably 3.0N / 20mm or more, more preferably 4.0N / 20mm or more, 5.0N / 20mm or more, 7.0N / 20mm or more, 10N / 20mm or more, or 12N / 20mm or more. The upper limit of the adhesive force after heating is not particularly limited, and from the viewpoint of the ease of manufacture and economy of the adhesive sheet, for example, it can be 50N / 20mm or less, 40N / 20mm or less, 30N / 20mm or less, or 25N / 20mm or less. In some schemes, from the viewpoint of improving the peelability achieved by the expansion of heat-expandable microspheres, the adhesive force N2 after heating can be, for example, 20N / 20mm or less, or 17N / 20mm or less. The pressure-sensitive adhesive sheet disclosed herein can also be preferably implemented in an embodiment in which the pressure-sensitive adhesive force N2 after heating is, for example, 13 N / 20 mm or less or 9 N / 20 mm or less.

[0059] Here, the initial adhesive strength [N / 20 mm] of the adhesive sheet is determined as follows: after being pressed onto a stainless steel (SUS) plate as an adherend and placed in an environment of 23°C and 50% RH for 30 minutes, the 180° peel adhesive strength is measured under the same environment (i.e., at 23°C) at a peel angle of 180 degrees and a tensile speed of 300 mm / min.

[0060] In addition, the adhesive strength [N / 20mm] of the adhesive sheet after heating is determined as follows: it is pressed onto a SUS plate as an adherend, heated for 5 minutes at a temperature 20°C lower than the expansion starting temperature T1 [°C] of the heat-expandable microspheres contained in the adhesive layer of the adhesive sheet as the evaluation object (hereinafter also referred to as "heating treatment temperature T2"), then placed under an environment of 23°C and 50% RH for 30 minutes, and then the 180° peeling adhesive strength is measured under the same environment (i.e., at 23°C) at a peeling angle of 180 degrees and a tensile speed of 300 mm / min.

[0061] As the adherend, a SUS304BA plate is used in the determination of any of the initial adhesive force, the adhesive force after heating, and the peel strength N3 after the expansion treatment described later. When conducting the measurement, a suitable backing material (e.g., a polyethylene terephthalate film with a thickness of about 25 μm) can be attached to the adhesive sheet as the object of measurement to enhance it as needed. More specifically, these adhesive forces can be measured according to the method described in the examples described later.

[0062] It should be noted that the adhesive force after heating of the adhesive sheet disclosed herein represents a characteristic of the adhesive sheet, and the use of the adhesive sheet is not limited to this. In other words, the use of the adhesive sheet disclosed herein is not limited to the method of increasing the adhesive force by heating at a heat treatment temperature T2 for 5 minutes after being pasted on the adherend, and can also be used in a method in which no special treatment is performed, such as heating to a room temperature region (usually 20°C to 30°C, typically 23°C to 25°C) or above. In this method of use, the adhesive force also increases for a long time, and a strong bond can be achieved. In addition, the adhesive sheet disclosed herein can promote the increase in adhesive force by heating at a temperature higher than 30°C and lower than the expansion starting temperature T1 at any time after pasting. The heating temperature T3 in the heat treatment is not particularly limited, and can be set in consideration of workability, economy, heat resistance of the substrate of the adhesive sheet or the adherend, etc. As long as the heating temperature T3 is less than the expansion starting temperature T1, there is no particular limitation. For example, it can be less than 170°C, less than 150°C, less than 120°C, less than 100°C, less than 80°C, or less than 70°C. In addition, the heating temperature T3 can be, for example, more than 40°C, more than 50°C, more than 60°C, more than 70°C, more than 80°C, or more than 100°C. The heating time is not particularly limited, for example, less than 1 hour, less than 30 minutes, less than 10 minutes, or less than 5 minutes. In addition, the heating time can be, for example, more than 1 minute, more than 3 minutes, more than 7 minutes, or more than 15 minutes. Alternatively, the heat treatment can be performed for a longer time within the limit that the adhesive sheet and the adherend do not suffer significant thermal degradation. It should be noted that the heat treatment can be performed once or multiple times.

[0063] In some schemes, the above-mentioned heating temperature T3 [℃] is preferably set to a temperature lower than the expansion starting temperature T1 [℃] by 5 ℃ or more, more preferably set to a temperature lower than 10 ℃ or more, and can be set to a temperature lower than 15 ℃ or more or 20 ℃ or more. By further increasing the above-mentioned temperature difference (T1-T3), it is possible to better suppress the situation in which the heat-expandable microspheres are not intentionally expanded due to the uneven temperature during the heating treatment for increasing the adhesive force. The upper limit of the temperature difference (T1-T3) is not particularly limited, for example, it can be set to below 150 ℃, from the viewpoint of the efficiency of the heating treatment, it can be set to below 125 ℃, it can be set to below 100 ℃, it can be set to below 80 ℃, it can be set to below 50 ℃.

[0064] (Expansion treatment)

[0065] The adhesive layer of the adhesive sheet disclosed herein can improve the peelability from the adherend by expanding the heat-expandable microspheres contained in the adhesive layer after being attached to the adherend (expansion treatment). For example, the adhesive layer containing the heat-expandable microspheres expands and deforms due to the expansion of the heat-expandable microspheres, and the adhesion to the adherend is reduced, thereby reducing the adhesive force. It is suitable that the heating temperature in the above-mentioned expansion treatment is usually set to the same degree or above the expansion starting temperature T1 of the heat-expandable microspheres (for example, a temperature higher than 5°C, 10°C or 15°C than the expansion starting temperature T1). The upper limit of the heating temperature in the above-mentioned expansion treatment is not particularly limited. From the viewpoint of heat resistance of the adherend or adhesive sheet, energy cost, etc., it is usually suitable to be set to below 250°C, preferably below 200°C, and can be set to below 180°C. The heating means used in the expansion treatment is not particularly limited, and one or more known heating means can be applied simultaneously or in stages. The non-limiting example of the above-mentioned heating means comprises a hot plate, a hot air dryer, an infrared lamp, hot water supply etc. The heat time in the thermal expansion treatment can be set in a suitable way that the expansion of heat-expandable microspheres occurs. In some schemes, from the viewpoint of the ease of process management, productivity, the above-mentioned heat time can be selected from, for example, about 1 second to 30 minutes, preferably from the scope of about 10 seconds to 15 minutes.

[0066] In some embodiments of the adhesive sheet disclosed herein, the adhesive force N3 after expansion treatment measured by the following steps (1) to (5) is preferably less than 1.0N / 20mm, and more preferably less than 0.5N / 20mm. Here, the adhesive force N3 [N / 20mm] after expansion treatment refers to the value of the 180° peeling adhesive force measured in the following step (5) for each 20mm wide measurement sample. Therefore, even if a portion of the area of ​​the measurement sample is peeled off and floated from the adherend due to the following step (4), it is not converted into the value of each 20mm wide portion of the measurement sample that is closely attached to the above-mentioned adherend. In addition, in the following step (5), when the tensile test cannot be appropriately performed because the measurement sample is extremely easy to peel off from the adherend (for example, when most of the area of ​​the measurement sample is peeled off and floated from the adherend due to the expansion treatment of the above (4)), it can be evaluated that the peelability at the expansion starting temperature T1 is good.

[0067] [Measurement procedure of peel strength N3 after expansion treatment]

[0068] (1) A PSA sheet to be evaluated was pressure-bonded to a SUS plate as an adherend to prepare a measurement sample.

[0069] (2) The measurement sample is heated for 5 minutes at a temperature (heat treatment temperature T2) 20°C lower than the expansion starting temperature T1[°C] of the heat-expandable microspheres contained in the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet.

[0070] (3) The above measurement sample was left to stand in an environment of 23°C and 50% RH for 30 minutes.

[0071] (4) Next, the measurement sample is heated at the expansion starting temperature T1 [° C.] for 5 minutes.

[0072] (5) After the above-mentioned measurement sample was left in an environment of 23°C and 50% RH for 30 minutes, the 180° peel adhesive strength was measured in the same environment (i.e., at 23°C) at a peel angle of 180 degrees and a tensile speed of 300 mm / min.

[0073] <Adhesive Layer>

[0074] Adhesive layer in the technology disclosed herein contains polymer A and heat-expandable microsphere as base polymer.Polymer A is the polymer of monomer raw material A.Above-mentioned adhesive layer can be formed by the adhesive composition containing complete polymer or partial polymer of monomer raw material A and heat-expandable microsphere.The form of adhesive composition is not particularly limited, can be various forms such as solvent-based, water-dispersible, hot-melt, active energy ray-curable (such as light-curable) etc.

[0075] (Heat-expandable microspheres)

[0076] As heat-expandable microsphere, it is not particularly limited and can be suitably selected from known heat-expandable microspheres (various inorganic heat-expandable microspheres, organic heat-expandable microspheres, etc.). As heat-expandable microsphere, from the viewpoint of easy mixed operation, it is suitable to use a foaming agent through microencapsulation. As this heat-expandable microsphere, for example, the material easily gasified and expanded by heating as isobutane, propane, pentane, etc. can be enumerated, and the microsphere obtained in the shell with elasticity, etc. can be included. The aforementioned shell is formed by hot-melt material, the situation that the material damaged by thermal expansion is more. As the material forming the aforementioned shell, for example, vinylidene chloride-acrylonitrile copolymer, polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polyacrylonitrile, polyvinylidene chloride, polysulfone, etc. can be enumerated.

[0077] Heat-expandable microspheres can be manufactured by conventional methods, such as coagulation method, interfacial polymerization method, etc. Heat-expandable microspheres can use, for example, the trade name "Matsumoto Microsphere" series (for example, trade name "Matsumoto MicrosphereF-30", "Matsumoto MicrosphereF-301D", "Matsumoto MicrosphereF-50D", "Matsumoto MicrosphereF-501D", "Matsumoto MicrosphereF-80SD", "Matsumoto MicrosphereF-80VSD", etc.) of Matsumoto Oil Pharmaceutical Co., Ltd.; and the trade name "051DU", "053DU", "551DU", "551-20DU", "551-80DU" of Expancel; and the commercially available products such as the trade name "Advancel" of Sekisui Chemical Co., Ltd.

[0078] The average particle size D of the heat-expandable microspheres can be appropriately selected according to the thickness Ta of the adhesive layer containing the heat-expandable microspheres. From the viewpoint of the smoothness of the adhesive layer surface (adhesive surface) attached to the adherend and avoiding the aggregation and destruction of the adhesive layer caused by the expansion of the heat-expandable microspheres, in some schemes, the average particle size of the heat-expandable microspheres can be, for example, less than 100 μm, less than 80 μm, less than 50 μm, less than 30 μm, less than 20 μm, less than 15 μm, or less than 13 μm. In addition, from the viewpoint of the handleability of the heat-expandable microspheres and the peeling effect caused by the expansion, in some schemes, the average particle size of the heat-expandable microspheres can be, for example, more than 1 μm, more than 3 μm, more than 5 μm, or more than 8 μm. Here, the average particle size refers to the particle size (50% volume average particle size) when the cumulative value in the volume-based particle size distribution obtained by the measuring device based on the laser diffraction scattering method is 50%. The particle size of the heat-expandable microspheres can be adjusted during the production process of the heat-expandable microspheres or after production by means of classification, etc. In some embodiments, heat-expandable microspheres having uniform particle sizes can be used.

[0079] The expansion starting temperature T1 of the heat-expandable microsphere is not particularly limited. From the viewpoint of avoiding the situation that the heat-expandable microsphere expands unintentionally when the adhesive sheet is not peeled off, it is usually suitable to be above 60°C, preferably above 70°C, can be above 80°C, can be above 90°C, can be above 100°C, can be above 120°C, can be above 140°C, can be above 160°C. In addition, from the viewpoint of the heat resistance and energy cost of the adherend, the expansion starting temperature T1 of the heat-expandable microsphere is usually suitable to be below 230°C, preferably below 210°C, more preferably below 200°C, can be below 180°C, can be below 150°C, can be below 130°C, can be below 100°C.

[0080] It should be noted that, in the present specification, the expansion starting temperature T1 of heat-expandable microspheres refers to the temperature at which the volume of the microcapsule starts to increase when measured at a heating rate of 10° C. / min using a thermomechanical analyzer.

[0081] From the viewpoint of efficiently and stably reducing the adhesive force to the adherend due to the expansion of the heat-expandable microspheres, the heat-expandable microspheres have an appropriate strength that does not break until the volume expansion rate is preferably 5 times or more, particularly 7 times or more, and particularly preferably 10 times or more.

[0082] The compounding amount of the heat-expandable microsphere in the adhesive layer is not particularly limited, can be set in the mode of suitably bringing into play the effect of improving strippability (reducing adhesive force) by expanding the heat-expandable microsphere.In some schemes, the content of heat-expandable microsphere relative to the base polymer (i.e. polymer A) 100 weight parts of adhesive layer can for example be set to more than 1 weight part, it is suitable to be usually set to more than 10 weight parts, it is suitable to be set to more than 25 weight parts, it is suitable to be set to more than 35 weight parts, it is suitable to be set to more than 50 weight parts, it is suitable to be set to more than 70 weight parts, it is suitable to be set to more than 85 weight parts.In addition, from the viewpoint of the adhesive layer before expanding the heat-expandable microsphere and the adhesion of adherend, it is suitable to be usually set to less than 200 weight parts for the content of heat-expandable microsphere relative to the base polymer 100 weight parts of adhesive layer, it is preferably set to less than 150 weight parts, it is more preferably set to less than 120 weight parts.

[0083] (foaming agent)

[0084] The adhesive layer of the adhesive sheet disclosed herein can further include a known foaming agent (a concept that does not contain heat-expandable microspheres) on the basis of including heat-expandable microspheres. As a foaming agent, various foaming agents such as various inorganic foaming agents and organic foaming agents can be appropriately selected and used. A foaming agent can be used alone or in combination of two or more. As a representative example of an inorganic foaming agent, for example, ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, various azides, etc. can be listed. Representative examples of organic foaming agents include water; chlorofluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarboxylate; hydrazide compounds such as p-toluenesulfonylhydrazide, diphenylsulfone-3,3'-disulfonylhydrazide, 4,4'-oxybis(benzenesulfonylhydrazide), and allylbis(sulfonylhydrazide); semicarbazide compounds such as p-styrenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholino-1,2,3,4-thiatriazole; nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide, and the like.

[0085] The amount of the foaming agent used can be, for example, in the range of 0.01 to 25 parts by weight relative to 100 parts by weight of the base polymer (i.e., polymer A) of the adhesive layer. From the viewpoint of the ease of controlling the timing of increasing or decreasing the adhesive force, the amount of the foaming agent used relative to 100 parts by weight of the base polymer is usually preferably set to 20 parts by weight or less, more preferably to 10 parts by weight or less, can be 5 parts by weight or less, can be 1 part by weight or less. Preferably, no foaming agent is used.

[0086] (Polymer A)

[0087] Polymer A is the base polymer of the adhesive layer containing the above-mentioned heat-expandable microspheres. Here, in this specification, the base polymer of the adhesive layer typically refers to the main component of the polymer component contained in the adhesive constituting the adhesive layer, that is, the component accounting for more than 50% by weight, which can be, for example, a component accounting for more than 75% by weight among the above-mentioned polymer components. In some embodiments, the above-mentioned polymer A is a component accounting for more than 50% by weight of the entire adhesive layer, which can be a component accounting for more than 70% by weight.

[0088] In the adhesive sheet disclosed herein, as the above-mentioned polymer A, one or more of various polymers showing rubber elasticity in the room temperature range, such as acrylic polymers, rubber polymers, polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, and fluorine polymers, which are well known in the adhesive field, can be used.

[0089] Glass transition temperature Tg of polymer A A There is no particular limitation and the Tg can be selected so as to obtain the preferred properties for the adhesive sheet disclosed herein. A The polymer A has a temperature lower than 0°C. The adhesive containing such a polymer A exhibits moderate fluidity (e.g., the mobility of the polymer chains contained in the adhesive), and is therefore suitable for realizing an adhesive sheet that can efficiently improve the adhesive force without expanding the heat-expandable microspheres. The adhesive sheet disclosed herein can be used with a Tg A It is convenient to implement the polymer A with a temperature of less than -10°C, less than -20°C, less than -30°C or less than -35°C. In some embodiments, Tg A It can be lower than -40℃, lower than -45℃. Tg A There is no particular lower limit for Tg. A is above -80°C, above -70°C or above -65°C for polymer A. In some embodiments, Tg A For example, the temperature may be -63°C or higher, -55°C or higher, -50°C or higher, or -45°C or higher.

[0090] Here, in this specification, the glass transition temperature (Tg) of a polymer refers to a nominal value recorded in literature, product catalogs, etc., or a Tg calculated using the Fox equation based on the composition of the monomer raw materials used in the preparation of the polymer. As shown below, the Fox equation refers to the relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0091] 1 / Tg=Σ(Wi / Tgi)

[0092] In the above Fox equation, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K). When the target polymer related to the specification of Tg is a homopolymer, the Tg of the homopolymer is consistent with the Tg of the target polymer.

[0093] As the glass transition temperature of the homopolymer used to calculate Tg, the value recorded in the known materials is used. Specifically, the numerical values ​​are listed in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). For monomers with multiple values ​​recorded in the above Polymer Handbook, the highest value is adopted.

[0094] As the glass transition temperature of a homopolymer of a monomer not described in the above-mentioned Polymer Handbook, a value obtained by the following measurement method was used.

[0095] Specifically, 100 parts by weight of monomer, 0.2 parts by weight of 2,2'-azobisisobutyronitrile and 200 parts by weight of ethyl acetate as a polymerization solvent were added to a reactor equipped with a thermometer, a stirrer, a nitrogen inlet pipe and a reflux condenser, and stirred for 1 hour while circulating nitrogen. After removing oxygen from the polymerization system by such operation, the temperature was raised to 63°C and reacted for 10 hours. Then, it was cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Then, the homopolymer solution was cast onto a release liner and dried to prepare a test sample (sheet homopolymer) with a thickness of about 2 mm. The test sample was punched into a disc shape with a diameter of 7.9 mm, clamped with parallel plates, and used a viscoelasticity testing machine (manufactured by TA Instruments Japan Inc., model name "ARES") to apply shear strain at a frequency of 1 Hz. The viscoelasticity was measured in a shear mode in a temperature range of -70°C to 150°C and a heating rate of 5°C / min. The temperature equivalent to the peak temperature of tanδ was recorded as the Tg of the homopolymer.

[0096] Although not particularly limited, the weight average molecular weight (Mw) of polymer A is generally about 20×10 4 The above is suitable. According to the Mw of polymer A, it is easy to obtain an adhesive showing good aggregation. The Mw of polymer A can be, for example, 30×10 4 Above, it can be 40×10 4 Above, it can be 50×10 4 From the perspective of obtaining a higher cohesive force, in some embodiments, the Mw of polymer A can be 60×10 4 Above, it can be 80×10 4 In addition, the Mw of polymer A is usually about 500×10 4 The following are suitable. The polymer A with this Mw is easy to form an adhesive that shows moderate fluidity (mobility of polymer chains), and is therefore suitable for achieving an adhesive sheet with low initial adhesion and high adhesion after the adhesion rises. In some embodiments, the Mw of polymer A can be, for example, 250×10 4 Below, it can be 200×10 4 Below, it can be 150×10 4 the following.

[0097] In addition, in this specification, Mw of polymer A and polymer B described later can be calculated|required by gel permeation chromatography (GPC) in terms of polystyrene. More specifically, Mw can be measured according to the method and conditions described in the Examples described later.

[0098] The storage modulus G' of polymer A at the expansion starting temperature T1 of heat-expandable microspheres (storage modulus G'(T1)) is not particularly limited, and can be, for example, 1×10 3 Pa~1×10 6 By making the storage modulus G' at the expansion starting temperature T1 not too low, the function of improving the peelability (reducing the adhesive force) by deforming the adhesive layer by the expansion of the heat-expandable microspheres can be appropriately demonstrated. From this point of view, the storage modulus G'(T1) is preferably 10 kPa (10×10 3 In addition, from the viewpoint of the adhesion before making the heat-expandable microsphere expand with adherend, storage modulus G '(T1) is usually suitable below 500kPa, is preferably below 300kPa, is more preferably below 150kPa, can be below 100kPa, can be below 80kPa, can be below 50kPa.

[0099] As the polymer A in the adhesive sheet disclosed herein, an acrylic polymer can be suitably used. In particular, in the scheme where the adhesive layer further comprises a polymer B described later on the basis of comprising polymer A, if an acrylic polymer is used as polymer A, there is a tendency to easily obtain good compatibility with polymer B. When polymer A has good compatibility with polymer B, it is preferred to reduce initial adhesion and improve adhesion after heating by improving the mobility of polymer B in the adhesive layer.

[0100] The acrylic polymer may be, for example, a polymer containing 50% by weight or more of monomer units derived from an alkyl (meth)acrylate, i.e., a polymer in which 50% by weight or more of the total amount of monomer components (monomer raw material A) used to prepare the acrylic polymer is an alkyl (meth)acrylate. As the alkyl (meth)acrylate, a monomer having 1 to 20 carbon atoms (i.e., C 1-20 (meth)acrylic acid alkyl ester having a linear or branched alkyl group. From the perspective of facilitating the balance of properties, the (meth)acrylic acid C in the monomer raw material A is preferably 1-20 The proportion of the alkyl ester may be, for example, 50% by weight or more, 60% by weight or more, or 70% by weight or more. 1-20The proportion of the alkyl ester may be, for example, 99.9 wt % or less, 98 wt % or less, or 95 wt % or less. In some embodiments, the (meth)acrylic acid C in the monomer raw material A 1-20 The ratio of the alkyl ester may be, for example, 90% by weight or less, 85% by weight or less, or 80% by weight or less.

[0101] As (meth)acrylic acid C 1-20 Specific non-limiting examples of the alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and (meth)acrylate. (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.

[0102] Among these, it is preferred to use at least (meth)acrylic acid C 1-18 Alkyl esters, more preferably at least (meth) acrylic acid C 1-14 In some embodiments, the acrylic polymer may contain a (meth)acrylic acid C 4-12 Alkyl ester (preferably acrylic acid C 4-10 Alkyl esters, such as acrylic acid C 6-10 For example, an acrylic polymer containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) as monomer units is preferred, and an acrylic polymer containing at least 2EHA is particularly preferred. Other (meth)acrylic acids C 1-18 Examples of the alkyl ester include methyl acrylate, methyl methacrylate (MMA), n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), and isostearyl acrylate (ISTA).

[0103] The monomer raw material A may contain other monomers (combination monomers) copolymerizable with the (meth) alkyl acrylate as the main component, as required. As the copolymerization monomer, a monomer having a polar group (e.g., a carboxyl group, a hydroxyl group, a ring containing a nitrogen atom, etc.) may be suitably used. The monomer having a polar group is beneficial for introducing a crosslinking point into the acrylic polymer or improving the cohesive force of the acrylic polymer. One type of copolymerization monomer may be used alone, or two or more types may be used in combination.

[0104] Specific non-limiting examples of the copolymerizable monomer include the following monomers.

[0105] Hydroxyl-containing monomers: for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, hydroxyalkyl (meth)acrylates such as (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, and the like.

[0106] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(methyl)acryloyl-2-pyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc.;

[0107] For example, monomers having a succinimide skeleton such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide;

[0108] For example, maleimides such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; and

[0109] For example, itaconimides such as N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, and N-lauryl itaconimide.

[0110] Carboxyl-containing monomers: for example, acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc.

[0111] Monomers containing anhydride groups: for example, maleic anhydride and itaconic anhydride.

[0112] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl (meth)acrylate glycidyl ether, allyl glycidyl ether, and glycidyl (meth)acrylate.

[0113] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.

[0114] Isocyanate group-containing monomers: for example, 2-isocyanatoethyl (meth)acrylate, etc.

[0115] Amide group-containing monomers: for example (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; monomers having hydroxyl groups and amide groups, for example N-(2-hydroxyethyl) (meth)acrylamide; N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl(meth)acrylamide such as N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide; and N,N-dimethylaminopropyl(meth)acrylamide, N-(meth)acryloylmorpholine, and the like.

[0116] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0117] Alkoxy-containing monomers: for example, alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; and alkoxyalkyl (meth)acrylates such as methoxyethylene glycol (meth)acrylate and methoxypolypropylene glycol (meth)acrylate.

[0118] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0119] (Meth)acrylates having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, and the like.

[0120] (Meth)acrylates having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like.

[0121] Vinyl ethers: vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0122] Vinyl esters: such as vinyl acetate, vinyl propionate, etc.

[0123] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0124] Olefins: such as ethylene, butadiene, isoprene, isobutylene, etc.

[0125] and heterocyclic-containing (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate; halogen-containing (meth)acrylates such as (meth)acrylates containing vinyl chloride and / or fluorine atoms; silicon-containing (meth)acrylates such as silicone (meth)acrylate; and (meth)acrylates obtained from terpene compound derivative alcohols.

[0126] When using this copolymerizable monomer, its amount is not particularly limited, and it is usually appropriate to set it to more than 0.01% by weight of the monomer raw material A. From the viewpoint of better exerting the effect brought about by the use of the copolymerizable monomer, the amount of the copolymerizable monomer can be set to more than 0.1% by weight of the monomer raw material A, can be set to more than 1% by weight, can be set to more than 2% by weight, more than 4% by weight or more than 6% by weight. In addition, the amount of the copolymerizable monomer can be set to less than 50% by weight of the monomer raw material A, preferably less than 45% by weight. Thus, the cohesive force of the adhesive is prevented from becoming too high, and the stickiness at room temperature (25°C) can be improved. In some schemes, the amount of the copolymerizable monomer can be less than 40% by weight of the monomer raw material A, and can be less than 35% by weight.

[0127] In some embodiments, the monomer raw material A may include a monomer having a ring containing a nitrogen atom. By using a monomer having a ring containing a nitrogen atom, the cohesion and polarity of the adhesive can be adjusted, and the adhesive strength after heating can be appropriately improved. By making the monomer raw material A include a monomer having a ring containing a nitrogen atom, there is a tendency that the compatibility of the polymer A formed by the above-mentioned monomer raw material A and the above-mentioned polymer B is improved. Thus, it is easy to obtain an adhesive sheet that can significantly increase the adhesive strength at a temperature lower than the expansion starting temperature T1.

[0128] The monomer having a ring containing a nitrogen atom can be appropriately selected from, for example, the above examples, and used alone or in combination of two or more. In some embodiments, the monomer raw material A preferably contains at least one monomer selected from the group consisting of N-vinyl cyclic amides represented by the following general formula (M1) as a monomer having a ring containing a nitrogen atom. The monomer raw material A may contain only one or more of the N-vinyl cyclic amides as monomers having a ring containing a nitrogen atom.

[0129]

[0130] Here, R in the above general formula (M1) 1 It is a divalent organic group.

[0131] Specific examples of N-vinyl cyclic amides include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazine-2-one, and N-vinyl-3,5-morpholinedione. N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam are particularly preferred.

[0132] The amount of the monomer having a ring containing a nitrogen atom is not particularly limited, and is generally suitable to be set to 0.01% by weight or more (preferably 0.1% by weight or more, for example 0.5% by weight or more) of the monomer raw material A. In some schemes, the amount of the monomer having a ring containing a nitrogen atom can be set to 1% by weight or more of the monomer raw material A, can be set to 5% by weight or more, can be set to 10% by weight or more, can be set to 12% by weight or more. In addition, from the viewpoint of improving the stickiness at room temperature (25°C) and improving the flexibility at low temperatures, the amount of the monomer having a ring containing a nitrogen atom is generally suitable to be set to 40% by weight or less of the monomer raw material A, can be set to 30% by weight or less, can be set to 20% by weight or less, can be set to 18% by weight or less.

[0133] In some preferred embodiments, the monomer raw material A contains a hydroxyl-containing monomer. By using a hydroxyl-containing monomer, the cohesion and polarity of the adhesive can be adjusted, and the adhesive strength after heating can be appropriately improved. In addition, the hydroxyl-containing monomer provides a site for reacting with a crosslinking agent (e.g., an isocyanate crosslinking agent) described later, and the cohesion of the adhesive can be improved through a crosslinking reaction.

[0134] As the hydroxyl-containing monomer, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, N-(2-hydroxyethyl) (meth)acrylamide, etc. can be suitably used. Among them, 2-hydroxyethyl acrylate (HEA), 4-hydroxybutyl acrylate (4HBA), and N-(2-hydroxyethyl)acrylamide (HEAA) can be cited as preferred examples.

[0135] The amount of the hydroxyl-containing monomer is not particularly limited, and is usually appropriate to be set to 0.01% by weight or more (preferably 0.1% by weight or more, for example 0.5% by weight or more) of the monomer raw material A. In some schemes, the amount of the hydroxyl-containing monomer can be set to 1% by weight or more of the monomer raw material A, can be set to 5% by weight or more, can be set to 10% by weight or more. In addition, from the viewpoint of improving the mobility of polymer B in the adhesive layer, the stickiness at room temperature (25°C), and improving the flexibility at low temperatures, the amount of the hydroxyl-containing monomer is usually appropriate to be set to 40% by weight or less of the monomer raw material A, can be set to 30% by weight or less, can be set to 20% by weight or less, can be set to 10% by weight or less, or 5% by weight or less.

[0136] In some schemes, as copolymerizable monomers, monomers (such as N-vinyl cyclic amides) having a ring containing nitrogen atoms and monomers containing hydroxyl groups can be used in combination. At this time, the total amount of monomers having a ring containing nitrogen atoms and monomers containing hydroxyl groups can be set to, for example, more than 0.1% by weight of the monomer raw material A, can be set to more than 1% by weight, can be set to more than 5% by weight, can be set to more than 10% by weight, can be set to more than 15% by weight, can be set to more than 20% by weight, can be set to more than 25% by weight. In addition, the total amount of monomers having a ring containing nitrogen atoms and monomers containing hydroxyl groups can be set to, for example, less than 50% by weight of the monomer raw material A, preferably less than 40% by weight.

[0137] In the embodiment in which the monomer raw material A contains a monomer having a nitrogen atom-containing ring and a hydroxyl group-containing monomer in combination, the content of the monomer having a nitrogen atom-containing ring in the monomer raw material A (W N ) and the content of hydroxyl-containing monomers (W OH ) is not particularly limited. N / W OH For example, it may be 0.01 or more, and is usually preferably 0.05 or more, and may be 0.1 or more, 0.2 or more, 0.5 or more, or 0.7 or more. N / W OH For example, it may be 100 or less, and is usually suitably 20 or less, and may be 10 or less, may be 5 or less, may be 2 or less, and may be 1.5 or less.

[0138] In some embodiments, the monomer raw material A preferably does not contain a monomer (monomer S1) having a polysiloxane skeleton as a constituent of the monomer raw material B described later, or the content of the monomer is less than 10% by weight (more preferably less than 5% by weight, for example less than 2% by weight) of the monomer raw material A. According to the monomer raw material A of such a composition, an adhesive sheet having both initial reprocessability and strong adhesion after the adhesion strength increases can be suitably realized. For the same reason, in other embodiments, the monomer raw material A preferably does not contain monomer S1, or when it contains monomer S1, its content (weight basis) is less than the content of monomer S1 in the monomer raw material B.

[0139] The method for obtaining polymer A is not particularly limited, and various polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately used. In some embodiments, solution polymerization can be appropriately used. The polymerization temperature during solution polymerization can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to, for example, about 20°C to 170°C (typically about 40°C to 140°C).

[0140] The initiator used for the polymerization can be appropriately selected from conventionally known thermal polymerization initiators, photopolymerization initiators, etc., depending on the polymerization method. The polymerization initiator can be used alone or in combination of two or more.

[0141] Examples of the thermal polymerization initiator include: azo-based polymerization initiators (e.g., 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride, etc.); persulfates such as potassium persulfate; peroxide-based polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, lauroyl peroxide, etc.); redox-based polymerization initiators, etc. The amount of the thermal polymerization initiator used is not particularly limited, and may be, for example, 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, based on 100 parts by weight of the monomer component (monomer raw material A) for preparing the acrylic polymer.

[0142] The photopolymerization initiator is not particularly limited, and for example, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, acylphosphine oxide photopolymerization initiators, etc. can be used. The amount of the photopolymerization initiator used is not particularly limited, and for example, it can be set to an amount in the range of 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the monomer raw material A.

[0143] In some embodiments, polymer A can be included in the adhesive composition for forming an adhesive layer in the form of a partial polymer (polymer slurry) obtained by irradiating ultraviolet rays (UV) to a mixture of the monomer raw material A as described above and a polymerization initiator to polymerize a part of the monomer component. The adhesive composition containing the polymer slurry can be applied to a predetermined coated object and irradiated with ultraviolet rays to complete the polymerization. That is, the polymer slurry can be used as a precursor of polymer A. The adhesive layer disclosed herein can be formed using, for example, an adhesive composition containing the polymer slurry and polymer B.

[0144] (Polymer B)

[0145] The adhesive sheet disclosed herein can be suitably realized by using an adhesive layer comprising a polymer A (e.g., an acrylic polymer) as described above, and a copolymer of a monomer having a polyorganosiloxane skeleton and a (meth) acrylic monomer, i.e., a polymer B. Such an adhesive layer can be formed from an adhesive composition containing a polymer A and a polymer B in the form of a complete polymer or a partial polymer of the monomer raw material A. The form of the adhesive composition is not particularly limited, and may be various forms such as a solvent type, a water-dispersible type, a hot melt type, an active energy ray curable type (e.g., a photocurable type), etc.

[0146] The polymer B in the technology disclosed herein is a copolymer of a monomer (hereinafter also referred to as "monomer S1") having a polyorganosiloxane skeleton and a (meth) acrylic acid monomer. Polymer B can function as an adhesive force increase delay agent that suppresses the initial adhesive force of the adherend by the low polarity and mobility of the polyorganosiloxane structure derived from monomer S1, and increases the adhesive force of the adherend by heating. As monomer S1, there is no particular limitation, and any monomer containing a polyorganosiloxane skeleton can be used. Monomer S1 promotes the uneven distribution of polymer B to the surface of the adhesive layer in the adhesive sheet before use (before being pasted on the adherend) due to the low polarity of its structure, showing light peelability (low adhesion) at the beginning of pasting. As monomer S1, a structure having a polymerizable reaction group at a single end is suitably used. According to the copolymerization of this monomer S1 and a (meth) acrylic acid monomer, a polymer B having a polyorganosiloxane skeleton in the side chain is formed. The polymer B of this structure is easy to form a polymer with low initial adhesive force and high adhesive force after heating due to the mobility and ease of movement of the side chain.

[0147] As the monomer S1, for example, a compound represented by the following general formula (1) or (2) can be used. More specifically, single-terminal reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd. include X-22-174ASX, X-22-2426, X-22-2475, and KF-2012. Monomer S1 can be used alone or in combination of two or more.

[0148]

[0149]

[0150] Here, R in the above general formulas (1) and (2) 3 is hydrogen or methyl, R 4 is a methyl group or a monovalent organic group, and m and n are integers greater than 0.

[0151] The functional group equivalent of monomer S1 can adopt a suitable value within the range of using the monomer S1 to exert the desired effect, and is not limited to a specific range. From the viewpoint of fully suppressing the initial adhesion, the functional group equivalent can be, for example, 140 g / mol or more, 200 g / mol or more, usually 300 g / mol or more (e.g., 500 g / mol or more) or more, preferably 700 g / mol or more, 800 g / mol or more, 850 g / mol or more, 1000 g / mol or more, or 1500 g / mol or more. In some schemes, from the viewpoint of both the initial low adhesion of the paste and the increase in adhesion over time, the functional group equivalent can be 2500 g / mol or more, 3000 g / mol or more, 4500 g / mol or more, 6000 g / mol or more, 9000 g / mol or more, 12000 g / mol or more, or 15000 g / mol or more (for example, 16000 g / mol or more). The functional group equivalent of monomer S1 can be, for example, 50000 g / mol or less. From the viewpoint of the increase in adhesion over time, the functional group equivalent is preferably, for example, 30000 g / mol or less, and more preferably 20000 g / mol or less. In some embodiments, the functional group equivalent weight of monomer S1 may be less than 18000 g / mol, less than 15000 g / mol, less than 10000 g / mol, less than 6000 g / mol, less than 5000 g / mol, less than 4000 g / mol or less than 3500 g / mol. If the functional group equivalent weight of monomer S1 is within the above range, it is easy to adjust the compatibility (e.g., compatibility with the base polymer) and mobility in the adhesive layer to a suitable range, and it is easy to achieve an adhesive layer with a high adhesion rise ratio.

[0152] Non-limiting examples of suitable ranges of the functional group equivalent weight of monomer S1 include 700 g / mol or more and 50,000 g / mol or less, 700 g / mol or more and 30,000 g / mol or less, 700 g / mol or more and 20,000 g / mol or less, 700 g / mol or more and less than 18,000 g / mol, 700 g / mol or more and less than 15,000 g / mol, 800 g / mol or more and less than 10,000 g / mol, 850 g / mol or more and less than 6,000 g / mol, and 1,500 g / mol or more and less than 5,000 g / mol. In some embodiments, suitable ranges of the functional group equivalent weight of monomer S1 may be 3000 g / mol to 50000 g / mol, 6000 g / mol to 50000 g / mol, 12000 g / mol to 50000 g / mol, or 15000 g / mol to 50000 g / mol.

[0153] Here, the so-called "functional group equivalent" refers to the weight of the main skeleton (e.g., polydimethylsiloxane) bonded to each functional group. The unit of notation is g / mol, which is converted to 1 mol of functional groups. The functional group equivalent of monomer S1 can be obtained, for example, by nuclear magnetic resonance (NMR) analysis. 1 It is calculated based on the spectral intensity of H-NMR (proton NMR). 1 The functional group equivalent (g / mol) of monomer S1 can be calculated based on the H-NMR spectrum intensity. 1 A general structural analysis method related to H-NMR spectral analysis is performed with reference to the description of Japanese Patent No. 5951153 as necessary.

[0154] It should be noted that when two or more monomers with different functional group equivalents are used as monomer S1, the functional group equivalent of monomer S1 can be an arithmetic mean. n The functional group equivalent of the monomer S1 composed of ) can be calculated by the following formula.

[0155] Functional group equivalent weight of monomer S1 (g / mol) = (functional group equivalent weight of monomer S11 × blending amount of monomer S11 + functional group equivalent weight of monomer S12 × blending amount of monomer S12 + ... + monomer S1 n Functional group equivalent × monomer S1 n The compounding amount of monomer S11 + the compounding amount of monomer S12 + ... + monomer S1 n Mixing amount)

[0156] The content of monomer S1 can be, for example, more than 5 wt % in the total amount of the monomer component (monomer raw material B) for preparing polymer B. From the viewpoint of better exerting the effect as an adhesive force rising retarder, it is preferably set to more than 10 wt %, can be set to more than 15 wt %, can be set to more than 20 wt %. In addition, from the viewpoint of polymerization reactivity and compatibility, the content of monomer S1 in monomer raw material B is suitable to be set to less than 60 wt %, can be set to less than 50 wt %, can be set to less than 40 wt %, can be set to less than 30 wt %. If the content of monomer S1 is less than 5 wt %, then it may not be possible to fully suppress the initial adhesive force. If the content of monomer S1 is more than 60 wt %, then the rise of the possible adhesive force becomes insufficient.

[0157] The monomer raw material B includes, in addition to the monomer S1, a (meth) acrylic acid monomer copolymerizable with the monomer S1. By copolymerizing one or more (meth) acrylic acid monomers with the monomer S1, the mobility of the polymer B in the adhesive layer can be appropriately adjusted. Copolymerizing the monomer S1 with the (meth) acrylic acid monomer is beneficial to improving the compatibility of the polymer B with the polymer A (e.g., acrylic acid polymer).

[0158] Examples of the (meth)acrylic acid monomer that can be used in the monomer raw material B include (meth)acrylic acid alkyl esters. For example, one or more of the monomers listed above as (meth)acrylic acid alkyl esters that can be used when the polymer A is an acrylic acid polymer can be used as constituent components of the monomer raw material B. In some embodiments, the monomer raw material B can contain (meth)acrylic acid C 4-12 Alkyl ester (preferably (meth) acrylic acid C 4-10 Alkyl esters, such as (meth) acrylic acid C 6-10 In other embodiments, the monomer raw material B may contain methacrylic acid C 1-18 Alkyl ester (preferably methacrylate C 1-14 Alkyl esters, such as methacrylate C 1-10 The monomer raw material B may contain, for example, one or more selected from MMA, BMA and 2EHMA as the (meth)acrylic monomer.

[0159] As other examples of the (meth)acrylic acid monomer, (meth)acrylic acid esters having an alicyclic hydrocarbon group can be cited. For example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, 1-adamantyl (meth)acrylate, etc. can be used. In some embodiments, the monomer raw material B can contain at least one selected from dicyclopentyl methacrylate, isobornyl methacrylate and cyclohexyl methacrylate as the (meth)acrylic acid monomer.

[0160] The content of the above-mentioned alkyl (meth)acrylate and the above-mentioned (meth)acrylate having an alicyclic hydrocarbon group in the monomer raw material B can be, for example, 10% by weight or more and 95% by weight or less, 20% by weight or more and 95% by weight or less, 30% by weight or more and 90% by weight or less, 40% by weight or more and 90% by weight or less, or 50% by weight or more and 85% by weight or less. From the perspective of the ease of controlling the rising behavior of the adhesive force, it is advantageous to use an alkyl (meth)acrylate. In some embodiments, the content of the (meth)acrylate having an alicyclic hydrocarbon group can be less than 50% by weight of the monomer raw material B, less than 30% by weight, less than 15% by weight, less than 10% by weight, or less than 5% by weight. It is also possible not to use a (meth)acrylate having an alicyclic hydrocarbon group.

[0161] In some preferred embodiments, the above-mentioned (meth) acrylic monomer as a constituent component of the monomer raw material B may include a monomer M2 whose homopolymer Tg is above 50°C. In polymer B, by copolymerizing monomer S1 and monomer M2, the mobility and mobility of the polyorganosiloxane structural part accompanying the temperature rise are appropriately controlled, and an adhesive sheet with a high adhesive force increase ratio is easily obtained. In some embodiments, the Tg of the homopolymer of monomer M2 may be above 60°C, above 70°C, above 80°C, or above 90°C. In addition, the upper limit of the Tg of the homopolymer of monomer M2 is not particularly limited, and from the viewpoint of the ease of synthesis of polymer B, it is generally appropriate to be below 200°C. In some embodiments, the Tg of the homopolymer of monomer M2 may be, for example, below 180°C, below 150°C, or below 120°C.

[0162] As the monomer M2, for example, among the (meth)acrylic monomers exemplified above, a monomer whose homopolymer Tg satisfies the conditions can be used. For example, one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid esters having an alicyclic hydrocarbon group can be used. As the (meth)acrylic acid alkyl ester, an alkyl methacrylate having an alkyl group with a carbon number of 1 to 4 can be suitably used.

[0163] In the scheme where the monomer raw material B includes the monomer M2, the content of the monomer M2 can be, for example, 5% by weight or more of the monomer raw material B, can be 10% by weight or more, can be 15% by weight or more, can be 20% by weight or more, can be 25% by weight or more, can be 30% by weight or more. In some schemes, the content of the above-mentioned monomer M2 can be 35% by weight or more of the monomer raw material B, can be 40% by weight or more, can be 45% by weight or more, can be 50% by weight or more, can be 55% by weight or more. In addition, the content of the above-mentioned monomer M2 can be, for example, 90% by weight or less, and it is usually suitable to be 80% by weight or less. In polymer B, by limiting the copolymerization ratio of the monomer M2 having a Tg of 50°C or more to a specific value or less, a good adhesion increase at a temperature lower than the expansion starting temperature T1 is exerted. In some schemes, the content of the monomer M2 is preferably 75% by weight or less, can be 70% by weight or less, can be 65% by weight or less, can be 60% by weight or less, can be 50% by weight or less, can be 45% by weight or less.

[0164] The content of the above-mentioned monomer M2 can be suitably applied in a scheme in which the monomer M2 includes one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters and the above-mentioned (meth)acrylic acid esters having an alicyclic hydrocarbon group, or a scheme in which the monomer M2 includes one or more monomers selected from (meth)acrylic acid alkyl esters (e.g., methacrylic acid alkyl esters). As a preferred example of this scheme, the scheme in which the above-mentioned monomer M2 includes MMA can be cited.

[0165] In some embodiments, the (meth) acrylic monomer may include a monomer M3 whose homopolymer Tg is less than 50°C (typically -20°C or more and less than 50°C). By using the monomer M3, it is easy to obtain a PSA sheet that has a good balance between the adhesive force and the cohesive force after the adhesive force increases. From the viewpoint of easily exerting this effect, the monomer M3 is preferably used in combination with the monomer M2.

[0166] As the monomer M3, for example, among the (meth)acrylic monomers exemplified above, a monomer whose homopolymer Tg satisfies the conditions can be used. For example, one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters can be used.

[0167] In the scheme where the monomer raw material B includes monomer M3, the content of monomer M3 can be, for example, more than 5% by weight of the monomer raw material B, can be more than 10% by weight, can be more than 15% by weight, can be more than 20% by weight, can be more than 25% by weight, can be more than 30% by weight, can be more than 35% by weight. In addition, it is suitable that the content of monomer M3 is usually set to less than 70% by weight of the monomer raw material B, can be less than 60% by weight, can be less than 50% by weight. The content of the above-mentioned monomer M3 can be suitably applied in a scheme where, for example, monomer M3 includes one or more monomers selected from (meth) alkyl acrylates (e.g., alkyl methacrylates).

[0168] In some embodiments of the adhesive sheet disclosed herein, the monomer raw material B preferably has a content of monomers having a homopolymer Tg higher than 170°C of 30% by weight or less. Here, in this specification, the content of a monomer of less than X% by weight refers to a concept including a scheme in which the content of the monomer is 0% by weight, that is, a scheme in which the monomer is substantially not contained, unless otherwise specified. In addition, substantially not containing means that at least the above-mentioned monomer is not actively used. By limiting the copolymerization ratio of the monomer having a homopolymer Tg higher than 170°C, it is easy to exert good adhesion increase at a temperature lower than the expansion starting temperature T1. In some embodiments, the content of the monomer having a homopolymer Tg higher than 170°C can be less than 20% by weight, can be less than 10% by weight, can be less than 5% by weight, and can be less than 2% by weight.

[0169] In some embodiments, the monomer raw material B preferably contains at least MMA as the (meth)acrylic monomer. According to the polymer B copolymerized with MMA, N 50 Large adhesive sheet. The proportion of MMA contained in the monomer raw material B in the total amount of (meth) acrylic acid monomers can be, for example, more than 5% by weight, more than 10% by weight, more than 20% by weight, more than 30% by weight, or more than 40% by weight. In some embodiments, the proportion of MMA in the total amount of the above-mentioned (meth) acrylic acid monomers can, for example, exceed 50% by weight, more than 55% by weight, more than 60% by weight, more than 65% by weight, or more than 70% by weight. In addition, the proportion of MMA in the total amount of the above-mentioned (meth) acrylic acid monomers is usually suitable to be less than 95% by weight, less than 90% by weight, or less than 85% by weight. In some preferred embodiments, from the perspective of the adhesive force increase at a temperature lower than the expansion starting temperature T1, the proportion of MMA in the total amount of the above-mentioned (meth) acrylic acid monomers can be less than 75% by weight, less than 65% by weight, less than 60% by weight, or less than 55% by weight (for example, less than 50% by weight).

[0170] Other examples of monomers that can be included together with monomer S1 as monomer units constituting polymer B include carboxyl group-containing monomers, acid anhydride group-containing monomers, hydroxyl group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, isocyanate group-containing monomers, amide group-containing monomers, monomers having a nitrogen atom-containing ring (N-vinyl cyclic amide, monomers having a succinimide skeleton, maleimides, itaconimides, etc.), (meth)acrylic acid aminoalkyl esters, vinyl esters, vinyl ethers, olefins, (meth)acrylates having an aromatic hydrocarbon group, heterocyclic ring-containing (meth)acrylates, halogen-containing (meth)acrylates, (meth)acrylates obtained from terpene compound derivative alcohols, and the like.

[0171] Other examples of monomers that can be included together with the monomer S1 as monomer units constituting the polymer B include: oxyalkylene di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; monomers having a polyoxyalkylene skeleton, such as polyethylene glycol, polypropylene glycol, etc. Polymerizable polyoxyalkylene ether having a polymerizable functional group such as (meth)acryloyl, vinyl, or allyl at one end of the polyoxyalkylene chain and an ether structure (alkyl ether, aryl ether, aryl alkyl ether, etc.) at the other end; alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; salts such as alkali metal (meth)acrylate; trimethylolpropane tri(meth)acrylate Poly (meth)acrylates: halogenated vinyl compounds such as vinylidene chloride and 2-chloroethyl (meth)acrylate; oxazoline-containing monomers such as 2-vinyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, and 2-isopropenyl-2-oxazoline; aziridine-containing monomers such as (meth)acryloylaziridine and 2-aziridineethyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and adducts of lactones and 2-hydroxyethyl (meth)acrylate, etc. Hydroxyl-containing vinyl monomers; fluorine-containing vinyl monomers such as fluorine-substituted (meth) alkyl acrylates; reactive halogen-containing vinyl monomers such as 2-chloroethyl vinyl ether and monochloroacetic acid vinyl; silicone-containing vinyl monomers such as vinyl trimethoxysilane, γ-(meth)acryloxypropyl trimethoxysilane, allyl trimethoxysilane, trimethoxysilylpropyl allylamine, and 2-methoxyethoxytrimethoxysilane; and macromonomers having a free radical polymerizable vinyl group at the end of a monomer obtained by polymerizing a vinyl group, etc. These monomers can be used alone or in combination of two or more and copolymerized with the monomer S1.

[0172] In some aspects of the PSA sheet disclosed herein, the composition of the (meth)acrylic acid-based monomer contained in the monomer raw material B is preferably such that the glass transition temperature Tg of the (meth)acrylic acid-based monomer composition is 0.0447 W / m. B [°C] is set to be lower than the expansion start temperature T1 [°C]. That is, T1-Tg B It is preferably 0° C. or higher. According to the polymer B, due to the mobility of the polymer B in a temperature range lower than the expansion starting temperature T1, the adhesive force can be greatly increased without expanding the heat-expandable microspheres.

[0173] The glass transition temperature Tg B Usually, the temperature is preferably 30°C or higher, more preferably 40°C or higher, and may be 45°C or higher, or 50°C or higher. B The high polymer B can maintain the reworkability during the period when the adhesive sheet attached to the adherend is required to be reworkable, even if the adhesive sheet is subjected to a temperature higher than room temperature due to heat generated by the operation of the equipment used in the manufacturing process, exhaust heat from adjacent equipment, etc. This is considered to be because: by appropriately increasing the Tg of the polymer B, the reworkability can be maintained appropriately. B The increase in the mobility and mobility of the polyorganosiloxane structure portion associated with the temperature rise is effectively suppressed by the monomer unit derived from the (meth)acrylic acid monomer contained in the polymer B, and the low adhesion caused by the presence of the polyorganosiloxane structure portion can be better maintained. In some embodiments, Tg B It may be 55°C or higher, 60°C or higher, 65°C or higher, or 70°C or higher. In addition, from the viewpoint of heat resistance of the adherend or the pressure-sensitive adhesive sheet, energy cost for heating treatment, etc., Tg B Usually, 150°C or less is suitable, preferably 120°C or less, more preferably 100°C or less, and may be 90°C or less, 85°C or less, 80°C or less, 70°C or less, 60°C or less, or 50°C or less.

[0174] From the viewpoint of efficiently achieving an increase in adhesive force without expanding the heat-expandable microspheres, the composition of the monomer raw material B is usually selected so that Tg B [℃] is 5℃ or more lower than the expansion start temperature T1[℃], that is, T1-Tg B It is appropriate to adjust the temperature to 5°C or more. B It can be 10°C or more, 15°C or more, preferably 20°C or more, more preferably 30°C or more, 40°C or more, 60°C or more, or 70°C or more. B Usually, the temperature is suitably 250°C or lower, and may be 200°C or lower, 150°C or lower, 100°C or lower, or 80°C or lower.

[0175] Here, the glass transition temperature Tg based on the above (meth)acrylic monomer composition is B It means the Tg calculated by the Fox equation based on the composition of only the (meth)acrylic acid monomer in the monomer components used to prepare the polymer B. Tg BIt can be calculated as follows: only the (meth)acrylic monomers among the monomer components used to prepare polymer B are taken as the object, and the glass transition temperature of the homopolymer of each (meth)acrylic monomer and the weight fraction of each (meth)acrylic monomer in the total amount of the (meth)acrylic monomer are calculated by applying the above-mentioned Fox formula. B From the perspective of the effect brought about, the total amount of monomer S1 and (meth)acrylic monomer present in all monomer components used to prepare polymer B can be, for example, 50% by weight or more, 70% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or substantially 100% by weight.

[0176] From the viewpoint of easily controlling the mobility of the polymer B in the adhesive layer, in some embodiments, the composition of the monomer raw material B is from the glass transition temperature Tg of the polymer A to the A Based on the relationship between Tg B Tg A 20℃ higher than Tg B -Tg A In some embodiments, Tg B -Tg A For example, it may be above 50°C, above 60°C, above 70°C, or above 80°C. In addition, in some embodiments, Tg B -Tg A For example, the temperature may be 150°C or lower, 140°C or lower, 130°C or lower, or 120°C or lower.

[0177] When heat treatment is performed to promote the increase of adhesive strength, the heating temperature T3 [° C.] in the heat treatment is preferably set to the glass transition temperature Tg B [°C] or higher, and more preferably, a temperature higher than the glass transition temperature Tg B [℃] High temperature (i.e. (T3-Tg B )>0). From the viewpoint of enhancing the effect of promoting the increase in adhesive strength, in some embodiments, the heating temperature T3 [°C] is related to the glass transition temperature Tg B [℃] Temperature difference (T3-Tg B ) can be set, for example, to 5°C or more, 10°C or more, 20°C or more, 40°C or more, or 60°C or more. The temperature difference (T3-Tg BThe upper limit of ) is not particularly limited, and may be, for example, 150°C or less. In consideration of workability, economic efficiency, heat resistance of the substrate of the adhesive sheet, and the adherend, in some embodiments, the temperature difference (T3-Tg B ) may be, for example, 100°C or less, 70°C or less, 50°C or less, or 35°C or less.

[0178] The glass transition temperature of polymer B (i.e., the glass transition temperature Tg based on the composition of monomer raw material B) Ball ) is not particularly limited and is selected so that the adhesive sheet disclosed herein can obtain preferred properties. Tg Ball For example, it can be less than 50°C, can be less than 30°C, can be less than 20°C, can be less than 15°C, can be less than 10°C. Ball When Tg is lowered, the mobility of the polymer B is improved, and the adhesive force tends to increase easily due to heating in a temperature range lower than the expansion starting temperature T1. Ball For example, it may be above -40°C, above -30°C, above -20°C, or above -10°C. Ball When the temperature is higher, reworkability tends to be easily maintained even when a temperature higher than room temperature is applied after the pressure-sensitive adhesive sheet is attached.

[0179] In some schemes, as polymer B, a polymer having no functional group that undergoes cross-linking reaction with polymer A can be suitably used. In other words, polymer B is preferably contained in the adhesive layer in a form that does not form a chemical bond with polymer A. The adhesive layer containing polymer B in this form has good mobility of polymer B when heated, which is suitable for improving the adhesion increase ratio. The functional group that undergoes cross-linking reaction with polymer A can vary according to the type of functional group possessed by the polymer A, and can be, for example, an epoxy group, an isocyanate group, a carboxyl group, an alkoxysilyl group, an amino group, etc.

[0180] The Mw of polymer B is not particularly limited. The Mw of polymer B may be, for example, 1000 or more, or 5000 or more. From the viewpoint of suitably showing an increase in adhesion at a temperature lower than the expansion starting temperature T1, the Mw of polymer B may be, for example, 10000 or more, 12000 or more, 15000 or more, or 20000 or more. In some embodiments, the Mw of polymer B may be 50000 or more, 80000 or more, 100000 or more, or 120000 or more (for example, 150000 or more). The upper limit of the Mw of polymer B may be, for example, 500000 or less, 350000 or less, less than 350000, or less than 100000. From the viewpoint of adjusting the compatibility and / or mobility within the adhesive layer to an appropriate range and increasing the adhesive force at a temperature lower than the expansion starting temperature T1, the Mw of polymer B may be less than 80,000, less than 70,000, less than 50,000, less than 40,000, less than 20,000, or further less than 10,000.

[0181] In some preferred embodiments, the Mw of polymer B is preferably less than the Mw of polymer A. Thus, it is easy to realize an adhesive sheet that takes into account both good reprocessability at the initial stage of pasting and increased adhesive strength at a temperature lower than the expansion starting temperature T1. The Mw of polymer B may be, for example, 0.8 times or less of the Mw of polymer A, 0.75 times or less, 0.5 times or less, 0.3 times or less, 0.1 times or less, 0.05 times or less, or 0.03 times or less (e.g., 0.02 times or less).

[0182] The polymer B can be produced by polymerizing the above-mentioned monomers by a known method such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, or photopolymerization.

[0183] A chain transfer agent may be used as needed to adjust the molecular weight of the polymer B. Examples of the chain transfer agent include compounds having a mercapto group such as octyl mercaptan, lauryl mercaptan, tert-nonyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol, and α-thioglycerol; thioglycolic acid esters such as thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, tert-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, ethylene glycol thioglycolate, neopentyl glycol thioglycolate, and pentaerythritol thioglycolate; α-methylstyrene dimer; and the like.

[0184] The amount of the chain transfer agent is not particularly limited, but is generally 0.05 to 20 parts by weight, preferably 0.1 to 15 parts by weight, and more preferably 0.2 to 10 parts by weight relative to 100 parts by weight of the monomer. By adjusting the amount of the chain transfer agent added in this way, a polymer B having a suitable molecular weight can be obtained. The chain transfer agent can be used alone or in combination of two or more.

[0185] As a means of adjusting the molecular weight of polymer B, various existing well-known means including the use of the above-mentioned chain transfer agent can be used alone or in combination. The same is true for the molecular weight of polymer A. Non-limiting examples of such means include the selection of polymerization method, the selection of the type or amount of polymerization initiator, the selection of polymerization temperature, the type and amount of polymerization solvent in solution polymerization, the selection of light irradiation intensity in photopolymerization, etc. Anyone skilled in the art can understand how to obtain a polymer with a desired molecular weight based on the description of this specification including the specific examples described later and the technical common sense at the time of this application.

[0186] In the adhesive sheet disclosed herein, the amount of polymer B can be set to, for example, 0.1 parts by weight or more relative to 100 parts by weight of polymer A, and can be set to 0.5 parts by weight or more, 1 part by weight or more, or 2 parts by weight or more from the viewpoint of obtaining a higher effect. In some schemes, from the viewpoint of improving reprocessability, the amount of the above-mentioned polymer B can be set to, for example, 3 parts by weight or more, 4 parts by weight or more, or 5 parts by weight or more. In addition, the amount of polymer B can be, for example, 75 parts by weight or less, 60 parts by weight or less, or 50 parts by weight or less relative to 100 parts by weight of polymer A. From the viewpoint of avoiding excessive reduction in the cohesive force of the adhesive layer, in some schemes, the amount of polymer B can be set to, for example, 40 parts by weight or less relative to 100 parts by weight of polymer A, or 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less. From the viewpoint of obtaining higher adhesion after heating, in some embodiments, the amount of the above-mentioned polymer B can be set to less than 20 parts by weight, can be set to less than 17 parts by weight, can be set to less than 15 parts by weight, can be set to less than 12 parts by weight, can be set to less than 10 parts by weight, can be set to less than 8 parts by weight, can be set to less than 6 parts by weight, can be set to less than 4 parts by weight (for example, less than 3 parts by weight).

[0187] Adhesive layer can contain polymer (arbitrary polymer) except polymer A and polymer B as required within the scope of not obviously damaging the adhesive sheet performance disclosed herein. It is suitable that the consumption of this arbitrary polymer is usually set to less than 20 weight % of the overall polymer component included in the adhesive layer, can be less than 15 weight %, can be less than 10 weight %. In some schemes, the consumption of the above-mentioned arbitrary polymer can be less than 5 weight % of the overall polymer component, can be less than 3 weight %, can be less than 1 weight %. It can also be an adhesive layer that does not substantially contain a polymer except polymer A and polymer B.

[0188] (Crosslinking agent)

[0189] In the adhesive layer, in order to adjust the cohesive force, a crosslinking agent can be used as needed. As the crosslinking agent, a crosslinking agent known in the adhesive field can be used, for example, epoxy crosslinking agents, isocyanate crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, etc. can be listed. In particular, isocyanate crosslinking agents, epoxy crosslinking agents, and metal chelate crosslinking agents can be preferably used. The crosslinking agent can be used alone or in combination of two or more.

[0190] Specifically, examples of isocyanate crosslinking agents include toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, polymethylene polyphenyl isocyanate, and adducts thereof with polyols such as trimethylolpropane. Alternatively, compounds having at least one isocyanate group and one or more unsaturated bonds in one molecule, specifically 2-isocyanatoethyl (meth)acrylate, etc., can also be used as isocyanate crosslinking agents. These can be used alone or in combination of two or more.

[0191] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin-type epoxy resins, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, diamine glycidylamine, N,N,N',N'-tetraglycidyl meta-xylylenediamine, and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, etc. These can be used alone or in combination of two or more.

[0192] Examples of the metal chelate compound include those containing aluminum, iron, tin, titanium, nickel, etc. as a metal component and acetylene, methyl acetoacetate, ethyl lactate, etc. as a chelate component. These may be used alone or in combination of two or more.

[0193] The amount used when using a cross-linking agent is not particularly limited, for example, can be set to an amount exceeding 0 weight part relative to 100 weight parts of polymer A. In addition, the amount of the cross-linking agent can be set to, for example, more than 0.01 weight part relative to 100 weight parts of polymer A, preferably more than 0.05 weight part. By increasing the amount of the cross-linking agent, the initial adhesive force of pasting is suppressed, and there is a tendency for reprocessability to improve. From the viewpoint of suppressing the aggregation and destruction of the adhesive layer caused by the expansion of heat-expandable microspheres, in some schemes, the amount of the cross-linking agent relative to 100 weight parts of polymer A can be more than 0.1 weight part, can be more than 0.5 weight part, can be more than 0.8 weight part, can be set to more than 1 weight part, can be set to more than 2 weight parts. On the other hand, from the viewpoint of appropriately allowing the mobility of polymer B and improving the adhesive force rising ratio, it is suitable that the amount of the cross-linking agent relative to 100 weight parts of polymer A is usually set to less than 15 weight parts, can be set to less than 10 weight parts, can be set to less than 5 weight parts.

[0194] The technology disclosed herein can be preferably implemented in a scheme using at least an isocyanate crosslinking agent as a crosslinking agent. From the viewpoint of both good reworkability at the initial stage of pasting and increased adhesive force at a temperature lower than the expansion starting temperature T1, in some schemes, the amount of the isocyanate crosslinking agent relative to 100 parts by weight of polymer A can be set to, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, or 0.8 parts by weight or more, 1 part by weight or more, or 2 parts by weight or more. In addition, it is suitable that the amount of the isocyanate crosslinking agent relative to 100 parts by weight of polymer A is usually set to 15 parts by weight or less, preferably 10 parts by weight or less, 7 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less.

[0195] Although not particularly limited, when an isocyanate crosslinking agent is used in the adhesive layer containing a hydroxyl group-containing monomer as a monomer unit, the amount of the hydroxyl group-containing monomer used is about 1: OH Relative to the amount of isocyanate crosslinking agent W NCO Based on weight, it can be set as W OH / W NCOBy increasing the amount of the hydroxyl-containing monomer relative to the isocyanate crosslinking agent in this way, a crosslinking structure suitable for significantly increasing the adhesive strength at a temperature lower than the expansion starting temperature T1 compared to the initial adhesive strength of the pasting can be formed. OH / W NCO It can be 3 or more, 5 or more, 10 or more, 20 or more, 30 or more, or 50 or more. OH / W NCO The upper limit of W is not particularly limited, but is set from the viewpoint of allowing a moderate migration of the polymer B caused by heating at a temperature lower than the expansion starting temperature T1. OH / W NCO For example, it may be 500 or less, may be 200 or less, may be 100 or less, or may be 50 or less.

[0196] In order to more effectively carry out the above-mentioned arbitrary cross-linking reaction, a cross-linking catalyst can also be used. As a cross-linking catalyst, for example, a tin catalyst (particularly dioctyltin dilaurate) can be preferably used. The amount of the cross-linking catalyst is not particularly limited, for example, relative to 100 parts by weight of polymer A, it can be approximately 0.0001 parts by weight to 1 part by weight.

[0197] A multifunctional monomer can be used in the adhesive layer as needed. The multifunctional monomer can be used in place of the crosslinking agent as described above or in combination with the crosslinking agent to help adjust the cohesive force, etc. For example, in the adhesive layer formed by a photocurable adhesive composition, a multifunctional monomer can be preferably used.

[0198] Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butanediol (meth)acrylate, and hexanediol di(meth)acrylate. Among them, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate can be preferably used. The polyfunctional monomer can be used alone or in combination of two or more.

[0199] The amount of the multifunctional monomer varies according to its molecular weight, number of functional groups, etc., and it is usually appropriate to set it to a range of about 0.01 to 3.0 parts by weight relative to 100 parts by weight of polymer A. In some schemes, the amount of the multifunctional monomer can be, for example, more than 0.02 parts by weight, or more than 0.03 parts by weight relative to 100 parts by weight of polymer A. By increasing the amount of the multifunctional monomer, the initial adhesive force of the paste is suppressed, and there is a tendency to improve reprocessability. On the other hand, from the viewpoint of ensuring the mobility of polymer B and suppressing its movement by a cross-linked network, regulating the adhesive force after heating at a temperature lower than the expansion starting temperature T1, the amount of the multifunctional monomer is less than 2.0 parts by weight relative to 100 parts by weight of polymer A, can be less than 1.0 parts by weight, and can be less than 0.5 parts by weight.

[0200] (Tackifying resin)

[0201] The adhesive layer may contain a tackifying resin as required. The tackifying resin is not particularly limited, and examples thereof include rosin-based tackifying resins, terpene-based tackifying resins, phenol-based tackifying resins, hydrocarbon-based tackifying resins, ketone-based tackifying resins, polyamide-based tackifying resins, epoxy-based tackifying resins, and elastic-based tackifying resins. The tackifying resins may be used alone or in combination of two or more.

[0202] Examples of the rosin-based tackifying resin include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin, modified rosins obtained by modifying these unmodified rosins by polymerization, disproportionation, hydrogenation, etc. (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, other chemically modified rosins, etc.), and various rosin derivatives.

[0203] Examples of the rosin derivatives include:

[0204] Rosin phenol resin obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and performing thermal polymerization;

[0205] Rosin ester resins such as rosin ester compounds obtained by esterifying unmodified rosin with alcohols (unmodified rosin esters), and modified rosin ester compounds obtained by esterifying modified rosin such as polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, and partially hydrogenated rosin with alcohols (polymerized rosin esters, stabilized rosin esters, disproportionated rosin esters, fully hydrogenated rosin esters, and partially hydrogenated rosin esters);

[0206] Unsaturated fatty acid-modified rosin resin obtained by modifying unmodified rosin or modified rosin (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, etc.) with unsaturated fatty acid;

[0207] Unsaturated fatty acid modified rosin ester resin obtained by modifying rosin ester resin with unsaturated fatty acid;

[0208] A rosin alcohol resin obtained by reducing the carboxyl groups in unmodified rosin, modified rosin (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, etc.), unsaturated fatty acid-modified rosin resin, and unsaturated fatty acid-modified rosin ester resin;

[0209] Metal salts of rosin-based resins (particularly rosin ester-based resins) such as unmodified rosin, modified rosin, and various rosin derivatives.

[0210] Examples of the terpene-based tackifier resin include terpene-based resins such as α-pinene polymers, β-pinene polymers, and dipentene polymers, and modified terpene-based resins obtained by modifying these terpene-based resins (phenol modification, aromatic modification, hydrogenation modification, hydrocarbon modification, etc.) (e.g., terpene phenol-based resins, styrene-modified terpene-based resins, aromatic-modified terpene-based resins, hydrogenated terpene-based resins, etc.), and the like.

[0211] Examples of the phenolic tackifying resin include condensates of various phenols (e.g., phenol, m-cresol, 3,5-xylenol, p-alkylphenol, resorcinol, etc.) and formaldehyde (e.g., alkylphenol resins, xylene formaldehyde resins, etc.), resol resins obtained by an addition reaction of the above phenols with formaldehyde using an alkali catalyst, and novolacs obtained by a condensation reaction of the above phenols with formaldehyde using an acid catalyst.

[0212] Examples of hydrocarbon-based tackifying resins include various hydrocarbon-based resins such as aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone indene resins.

[0213] Examples of commercially available polymerized rosin esters that can be suitably used include, but are not limited to, trade names “PENSEL D-125,” “PENSEL D-135,” “PENSEL D-160,” “PENSEL KK,” and “PENSEL C” manufactured by Arakawa Chemical Industries, Ltd.

[0214] Examples of commercially available terpene-phenol resins that can be suitably used include, but are not limited to, "YS POLYSTAR S-145", "YS POLYSTAR G-125", "YS POLYSTAR N125", and "YS POLYSTAR U-115" manufactured by YASUHARA CHEMICAL Co., Ltd., "Tamanol 803L" and "Tamanol 901" manufactured by Arakawa Chemical Industries, Ltd., and "SUMILITERESIN PR-12603" manufactured by Sumitomo Bakelite Co., Ltd.

[0215] The content of the tackifier resin is not particularly limited and can be set so as to exhibit appropriate adhesive properties according to the purpose and application. The content of the tackifier resin (the total amount of two or more tackifier resins when included) can be set to about 5 to 500 parts by weight relative to 100 parts by weight of the polymer A.

[0216] As the tackifying resin, a resin having a softening point (softening temperature) of about 80°C or more (preferably about 100°C or more, for example, about 120°C or more) is preferably used. A tackifying resin having a softening point above the above lower limit value can easily obtain an adhesive sheet having high adhesive force after heating. The upper limit of the softening point is not particularly limited, for example, it can be about 200°C or less (typically 180°C or less). It should be noted that the softening point of the tackifying resin can be measured based on the softening point test method (ring and ball method) specified in JIS K2207.

[0217] In addition, the adhesive layer in the technology disclosed herein may also contain known additives that can be used for adhesives, such as leveling agents, plasticizers, softeners, colorants (dyes, pigments, etc.), fillers, antistatic agents, antioxidants, ultraviolet absorbers, antioxidants, light stabilizers, preservatives, etc., as needed within the range that does not significantly hinder the effects of the present invention.

[0218] The adhesive layer constituting the adhesive sheet disclosed herein can be a cured layer of an adhesive composition. That is, the adhesive layer can be formed by applying (e.g., coating) an adhesive composition such as a water-dispersible, solvent-based, light-curable, or hot-melt adhesive composition to an appropriate surface and then appropriately implementing a curing treatment. When two or more curing treatments (drying, crosslinking, polymerization, cooling, etc.) are performed, they can be performed simultaneously or in multiple stages. In an adhesive composition using a partial polymer (polymer slurry) of a monomer raw material, typically, as the above-mentioned curing treatment, a final copolymerization reaction is performed. That is, the partial polymer is further provided for a copolymerization reaction to form a complete polymer. For example, if it is a photocurable adhesive composition, light irradiation is implemented. Curing treatments such as crosslinking and drying can also be implemented as needed. For example, in the case of a photocurable adhesive composition and it is necessary to dry it, photocuring can be performed after drying. In an adhesive composition using a complete polymer, typically, as the above-mentioned curing treatment, drying (heat drying), crosslinking, etc. are implemented as needed.

[0219] The pressure-sensitive adhesive composition can be applied using a conventional coater such as a gravure roll coater, a reverse roll coater, a lick roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater.

[0220] The thickness of the adhesive layer is not particularly limited, and can be set to, for example, 3 μm or more. From the viewpoint of suppressing the reduction of the smoothness of the adhesive surface caused by containing heat-expandable microspheres, the thickness of the adhesive layer is usually more than 7 μm, preferably more than 10 μm, more than 15 μm, more than 25 μm, and more than 35 μm. The upper limit of the thickness of the adhesive layer is not particularly limited, and it is usually suitable to be less than 300 μm, less than 200 μm, less than 150 μm, less than 100 μm, and less than 70 μm. From the viewpoint of avoiding aggregation damage of the adhesive layer caused by the expansion of heat-expandable microspheres, it is advantageous that the thickness of the adhesive layer is not too large. In some schemes, the thickness of the adhesive layer can be less than 60 μm, less than 50 μm, and less than 45 μm.

[0221] The thickness Ta of adhesive layer is preferably greater than the average particle diameter D of heat-expandable microspheres. That is, Ta / D is preferably greater than 1.0. From the viewpoint of the smoothness of bonding surface, in some schemes, Ta / D is preferably more than 2.0, can be more than 3.0, can be more than 4.0. In addition, from the viewpoint of the peeling effect realized by the expansion of heat-expandable microspheres that is easily brought into play, Ta / D is generally suitable for less than 50, is preferably less than 20, can be less than 15, can be less than 10.

[0222] It should be noted that, in the case of an adhesive sheet having a first adhesive layer and a second adhesive layer on the first and second sides of substrate, the thickness of the above-mentioned adhesive layer can at least be applied to the thickness of the first adhesive layer. The thickness of the second adhesive layer can also be selected from the same range. In addition, in the case of an adhesive sheet without substrate, the thickness of the adhesive sheet is consistent with the thickness of the adhesive layer.

[0223] In addition, in the adhesive sheet disclosed herein, the adhesive layer (comprising the first adhesive layer with heat-expandable microspheres on the first side, the second side of base material, in the adhesive sheet of the second adhesive layer, is each adhesive layer) that comprises heat-expandable microspheres can be a single-layer structure, can also be a multilayer structure of more than two layers.From the viewpoint of the controllability of the adhesive force before the expansion of heat-expandable microspheres, in some schemes, adhesive layer is preferably a single-layer structure.

[0224] <Supporting Base Material>

[0225] The adhesive sheet of some embodiments can be in the form of an adhesive sheet with a substrate having an adhesive layer on one or both sides of the supporting substrate. The material of the supporting substrate is not particularly limited and can be appropriately selected according to the purpose of use, the mode of use, etc. of the adhesive sheet. As non-limiting examples of usable substrates, there can be listed: polyolefin films with polyolefins such as polypropylene and ethylene-propylene copolymer as the main component, polyester films with polyesters such as polyethylene terephthalate and polybutylene terephthalate as the main component, and plastic films such as polyvinyl chloride films with polyvinyl chloride as the main component; foam sheets formed by foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; various fibrous materials (which can be natural fibers such as hemp and cotton, synthetic fibers such as polyester and vinylon, semi-synthetic fibers such as acetate, etc.) Fabrics and non-woven fabrics obtained alone or by blending, etc.; Japanese paper, high-quality paper, kraft paper, crepe paper, etc.; metal foils such as aluminum foil and copper foil, etc. It can also be a substrate composed of them. Examples of such a composite substrate include a substrate having a structure in which a metal foil and the above-mentioned plastic film are laminated, and a plastic substrate reinforced with inorganic fibers such as glass cloth.

[0226] As the substrate of the adhesive sheet disclosed herein, various film substrates can be preferably used. The above-mentioned film substrate can also be a porous substrate such as a foam film, a non-woven fabric sheet, etc., can also be a non-porous substrate, and can also be a substrate of a structure in which a porous layer and a non-porous layer are stacked. In some embodiments, as the above-mentioned film substrate, it is preferred to use a substrate containing a (self-supporting or non-dependent) resin film that can independently maintain the shape as a base film. Here, the so-called "resin film" refers to a non-porous structure, typically a (non-porous) resin film that does not substantially contain bubbles. Therefore, the above-mentioned resin film is a concept that is distinguished from a foam film and a non-woven fabric. As the above-mentioned resin film, a film that can independently maintain the shape (self-supporting or non-dependent) can be suitably used. The above-mentioned resin film can be a single-layer structure, or it can be a multilayer structure (such as a three-layer structure) of more than two layers.

[0227] As the resin material constituting the resin film, for example, polyester, polyolefin, nylon 6, nylon 66, partially aromatic polyamide, such as polyamide (PA), polyimide (PI), polyamide-imide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polytetrafluoroethylene (PTFE) and other fluororesins, acrylic resins, polyacrylates, polystyrene, polyvinyl chloride, polyvinylidene chloride and other resins can be used. The above-mentioned resin film can be a film formed by using a resin material containing one such resin alone, or a film formed by using a resin material blended with two or more such resins. The above-mentioned resin film can be an unstretched film, or a film stretched (for example, uniaxially stretched or biaxially stretched).

[0228] Suitable examples of resin materials constituting the resin film include polyester resins, PPS resins, and polyolefin resins. Here, the so-called polyester resin refers to a resin containing polyester in a ratio exceeding 50% by weight. Similarly, PPS resin refers to a resin containing PPS in a ratio exceeding 50% by weight, and polyolefin resin refers to a resin containing polyolefin in a ratio exceeding 50% by weight.

[0229] As the polyester resin, a polyester resin containing a polyester obtained by polycondensing a dicarboxylic acid and a diol as a main component is typically used. Specific examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate, etc.

[0230] As the polyolefin resin, one polyolefin can be used alone or in combination of two or more polyolefins. The polyolefin can be, for example, a homopolymer of α-olefin, a copolymer of two or more α-olefins, a copolymer of one or more α-olefins and other vinyl monomers, etc. As specific examples, ethylene-propylene copolymers such as polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, ethylene-ethyl acrylate copolymers, etc. can be listed. Both low-density (LD) polyolefins and high-density (HD) polyolefins can be used. Examples of polyolefin resin films include: unstretched polypropylene (CPP) film, biaxially stretched polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, medium-density polyethylene (MDPE) film, high-density polyethylene (HDPE) film, polyethylene (PE) film obtained by blending two or more polyethylene (PE), PP / PE blended film obtained by blending polypropylene (PP) and polyethylene (PE), etc.

[0231] For the specific example of the resin film that can be used as the base film of the adhesive sheet disclosed herein and preferably utilized, PET film, PEN film, PPS film, PEEK film, CPP film and OPP film can be listed. As the example of the preferred base film from the viewpoint of strength and dimensional stability, PET film, PEN film, PPS film and PEEK film can be listed. From the viewpoint of the ease of obtaining the substrate, PET film and PPS film are particularly preferred, wherein, PET film is preferably used.

[0232] In the resin film, within the range that does not significantly impair the effect of the present invention, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, lubricants, and anti-blocking agents can be mixed as needed. The mixing amount of the additives is not particularly limited and can be appropriately set according to the use of the adhesive sheet, etc.

[0233] The method for producing the resin film is not particularly limited, and for example, conventionally known general resin film forming methods such as extrusion molding, inflation molding, T-die casting, and calender roll molding can be appropriately used.

[0234] The substrate may be a substrate substantially composed of such a base film. Alternatively, the substrate may be a substrate further comprising an auxiliary layer in addition to the base film. Examples of the auxiliary layer include: an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printing layer for giving the substrate a desired appearance, a laminating layer, an antistatic layer, a primer layer, a peeling layer and other surface treatment layers.

[0235] The thickness of the substrate is not particularly limited and can be selected according to the purpose and method of use of the adhesive sheet. The thickness of the substrate can be, for example, 1000 μm or less. In some schemes, from the perspective of the handling and processing of the adhesive sheet, the thickness of the substrate can be, for example, 500 μm or less, 300 μm or less, 250 μm or less, or 200 μm or less. From the perspective of miniaturization and lightweight of products to which the adhesive sheet is applied, in some schemes, the thickness of the substrate can be, for example, 160 μm or less, 130 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 25 μm or less, 10 μm or less, or 5 μm or less. If the thickness of the substrate becomes smaller, there is a tendency for the softness of the adhesive sheet and the followability of the adherend surface shape to be improved. In addition, from the viewpoint of handling, processability, etc., the thickness of the substrate can be, for example, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 25 μm or more, or more than 25 μm. In some embodiments, the thickness of the substrate can be, for example, 30 μm or more, 35 μm or more, 55 μm or more, 70 μm or more, 75 μm or more, 90 μm or more, or 120 μm or more. For example, in an adhesive sheet that can be used for the purpose of strengthening, supporting, mitigating impact, etc. of an adherend, a substrate with a thickness of 30 μm or more can be appropriately used.

[0236] The first side of the substrate may be subjected to corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and the like, and the existing known surface treatments such as the formation of a primer layer by coating a primer (primer) as required. This surface treatment may be a treatment for improving the anchoring property of the adhesive layer to the substrate (including the direct anchoring property of the adhesive layer directly laminated on the substrate to the substrate, and the indirect anchoring property of the adhesive layer laminated on the substrate through other layers such as an elastic intermediate layer to the substrate. The same below). For example, in an adhesive sheet having a substrate including a resin film as a base film, a substrate to which the anchoring property improvement treatment has been applied may be suitably adopted. The above-mentioned surface treatment may be applied alone or in combination. The composition of the primer for forming the primer layer is not particularly limited, and may be suitably selected from known materials. The thickness of the primer layer is not particularly limited, and is usually suitable for about 0.01 μm to 1 μm, preferably about 0.1 μm to 1 μm. As other treatments that may be applied to the first side of the substrate as required, antistatic layer formation treatment, coloring layer formation treatment, printing treatment, etc. may be cited.

[0237] When the adhesive sheet disclosed herein is a single-sided adhesive sheet with an adhesive layer only on the first side of the substrate, the existing known surface treatments such as peeling treatment and antistatic treatment can be implemented on the second side of the substrate as needed. For example, by surface treating the back side of the substrate with a peeling agent (typically, by using a peeling agent to set a peeling layer), the unwinding force of the adhesive sheet wound into a roll-shaped form can be reduced. As a peeling agent, a silicone-based peeling agent, a long-chain alkyl-based peeling agent, an olefin-based peeling agent, a fluorine-based peeling agent, a fatty acid amide-based peeling agent, molybdenum sulfide, silicon dioxide powder, etc. can be used. In addition, for the purpose of improving printability, reducing light reflectivity, improving repeated adhesion, etc., the second side of the substrate can be implemented with corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment and other treatments. In addition, in the case of two-sided adhesive sheets, the second side of the substrate can be implemented as required with the surface treatment that can be implemented on the first side of the substrate and the same surface treatment in the above-mentioned example. It should be noted that the surface treatment implemented on the first side of the substrate can be the same or different from the surface treatment implemented on the second side.

[0238] <Elastic middle layer>

[0239] Adhesive sheet disclosed herein can include an elastic intermediate layer configured between substrate and adhesive layer. The elastic intermediate layer is a layer provided as required, and is not necessarily provided. By sandwiching the elastic intermediate layer between substrate and adhesive layer, the anchoring property of the adhesive layer for the above-mentioned substrate can be improved. For example, by heating, the heat-expandable microspheres in the above-mentioned adhesive layer are expanded, so as to improve the peeling property of the adhesive sheet from the adherend, for the adherend, the adhesive force reduction effect caused by the above-mentioned expansion can be effectively exerted, and the adhesive layer is suitably maintained to be joined to the form of the supporting substrate by means of the elastic intermediate layer. The back side of the adhesive layer (the side opposite to the face attached to the adherend) is provided with an elastic intermediate layer, which can also be beneficial to improve the peeling property by making the heat-expandable microspheres expand by heating. For example, when the adhesive layer expands with the expansion of the above-mentioned heat-expandable microspheres, the constraint of the expansion in the surface direction of the adhesive sheet can be reduced, and the formation of the corrugated structure realized by the shape of the adhesive layer becoming three-dimensional (such as the occurrence of warping) is promoted, and the adhesive sheet is peeled off (floating) from the adherend. Furthermore, when the PSA sheet is attached to an adherend, the deformability of the elastic intermediate layer can improve the adhesion between the PSA layer surface and the adherend surface.

[0240] In some aspects, the hardness of the elastic intermediate layer is, for example, preferably 50 or less, more preferably 40 or less, as measured by a durometer based on ASTM D-2240 and using a type D durometer (Shore D).

[0241] In some embodiments, an adhesive may be suitably used as a constituent material of the elastic intermediate layer. The adhesive constituting the elastic intermediate layer is not particularly limited and may be suitably selected from various known adhesives such as acrylic adhesives using acrylic polymers as base polymers, rubber adhesives using rubbers such as natural rubber or synthetic rubber as base polymers, vinyl alkyl ether adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, styrene-diene block copolymer adhesives, creep property improved adhesives, and radiation curing adhesives. In addition, the adhesive component that can be used in the above-mentioned adhesive layer may be suitably used as a constituent material of the elastic intermediate layer.

[0242] When the base polymer of the adhesive used in the elastic intermediate layer (hereinafter also referred to as "polymer I") is an acrylic polymer, the acrylic polymer may be a polymer containing, as a main monomer (a component accounting for 50% by weight or more of the monomer raw material used to prepare the acrylic polymer), a monomer raw material of (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 20 or less, such as methyl, ethyl, propyl, butyl, 2-ethylhexyl, isooctyl, isononyl, isodecyl, dodecyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, etc. The monomer raw material used to prepare the polymer I may further contain one or more secondary monomers selected from acrylic acid, methacrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, N-hydroxymethyl acrylamide, acrylonitrile, methacrylonitrile, glycidyl acrylate, glycidyl methacrylate, vinyl acetate, styrene, isoprene, butadiene, isobutylene, vinyl ether, etc.

[0243] When the base polymer (polymer A) of the adhesive layer that comprises heat-expandable microsphere is an acrylic polymer, from the viewpoint of the affinity of adhesive layer and elastic interlayer, as the base polymer (polymer I) of elastic interlayer, can suitably adopt acrylic polymer.Above-mentioned polymer I can be selected from the polymer identical with the acrylic polymer that can be used as polymer A.

[0244] The elastic intermediate layer is not limited to the layer formed by using the adhesive as described above. The elastic intermediate layer can be formed by using one or more elastic materials selected from, for example, natural rubber; synthetic rubbers such as nitrile, diene, and acrylic resins; thermoplastic elastomers such as polyolefins and polyesters; synthetic resins having rubber elasticity such as ethylene-vinyl acetate copolymers, polyurethane, polybutadiene, and soft polyvinyl chloride.

[0245] The above-mentioned adhesive or the above-mentioned elastic material constituting the elastic intermediate layer may contain known additives such as crosslinking agent, tackifying resin, leveling agent, plasticizer, softener, colorant (dyes, pigments, etc.), filler, antistatic agent, antioxidant, ultraviolet absorber, antioxidant, light stabilizer, preservative, etc. as needed. The above-mentioned crosslinking agent, as an arbitrary component of the adhesive layer, can be appropriately selected and used from the crosslinking agents exemplified above. The amount of the above-mentioned crosslinking agent in the elastic intermediate layer can be selected from the amount of the crosslinking agent in the adhesive layer and in the range of the above examples. The above-mentioned tackifying resin can be appropriately selected and used from the tackifying resin exemplified above, for example, as an arbitrary component of the adhesive layer. The amount of the above-mentioned tackifying resin in the elastic intermediate layer can be selected from the amount of the tackifying resin in the adhesive layer and in the range of the above examples.

[0246] In some schemes, the elastic interlayer can be a composition that does not contain heat-expandable microspheres or whose content is limited. In this scheme, the weight ratio of heat-expandable microspheres in the elastic interlayer as a whole is usually less than 5 wt % is suitable, preferably less than 1 wt %, more preferably less than 0.5 wt %. For example, the elastic interlayer that does not contain heat-expandable microspheres can be suitably adopted.

[0247] The method for forming the elastic intermediate layer is not particularly limited, and an appropriate method may be adopted from the following methods, for example, a method of coating a coating liquid containing an elastic intermediate layer forming material on a substrate (coating method); a method of bonding a film formed of the elastic intermediate layer forming material to a substrate, or a method of bonding a laminated film obtained by forming a layer formed of the elastic intermediate layer forming material on the back side of the adhesive layer (the side opposite to the side attached to the adherend) to a substrate (dry lamination method); a method of co-extruding a substrate forming material and an elastic intermediate layer forming material (coextrusion method), etc.

[0248] The elastic intermediate layer may be composed of a foamed film (e.g., polyethylene foam, polyurethane foam, etc.). Foaming may be performed by conventional methods, such as a method based on mechanical stirring, a method using reaction-generated gas, a method using a foaming agent, a method of removing soluble substances, a method based on spraying, a method of forming a composite foam, a sintering method, etc.

[0249] The thickness of the elastic intermediate layer is not particularly limited, and can be set in a manner that the desired effect is exerted by setting the elastic intermediate layer. The thickness of the elastic intermediate layer can be set, for example, to be 0.1 μm or more, 1 μm or more, or 5 μm or more. From the viewpoint of better exerting the effect brought about by setting the elastic intermediate layer, the thickness of the elastic intermediate layer is usually more than 10 μm, and from the viewpoint of reducing the constraint of expansion in the surface direction of the adhesive sheet, it is advantageous to be more than 25 μm, for example, it can be more than 50 μm, it can be more than 75 μm, it can be more than 100 μm, it can exceed 100 μm, it can be more than 125 μm, and it can be more than 150 μm. In addition, from the viewpoint of the handling and processing properties of the adhesive sheet, the thickness of the elastic intermediate layer is usually less than 1000 μm, preferably less than 500 μm, it can be less than 300 μm, and it can be less than 200 μm.

[0250] The elastic intermediate layer may be a single-layer structure or a multi-layer structure including two or more sub-layers. The thickness of each sub-layer may be, for example, 0.1 μm or more, and is usually preferably 5 μm or more, and may be 10 μm or more, 25 μm or more, 40 μm or more, or 60 μm or more. In addition, the thickness of each sub-layer may be, for example, 300 μm or less, and is preferably 200 μm or less, and more preferably 100 μm or less from the viewpoint of suppressing the aggregation failure of the elastic intermediate layer.

[0251] The elastic intermediate layer of the multilayer structure may have a support sheet between adjacent sublayers. The support sheet is beneficial to suppress the aggregation failure of the elastic intermediate layer, improve the processability of the adhesive sheet, etc. For example, when the elastic intermediate layer is thicker (for example, when the thickness is more than 50μm, more than 100μm or more than 125μm), it is appropriate to use an elastic intermediate layer of a multilayer structure containing at least one support sheet between the sublayers. The support sheet can be appropriately selected and used from various plastic films, foam sheets, woven fabrics, non-woven fabrics, papers, metal foils, and sheets composed of them in the same manner as the above-mentioned supporting substrate. As examples of support sheets that can be appropriately used, non-woven fabrics and plastic films can be listed. The thickness of the non-woven fabric can be, for example, more than 10μm, more than 20μm, more than 50μm, and in addition, it is usually appropriate to be less than 120μm, less than 100μm, or less than 80μm. The thickness of the plastic film is usually preferably 20 μm or less, preferably 15 μm or less, 10 μm or less, or 5 μm or less, and usually 2 μm or more, from the viewpoint of flexibility of the elastic intermediate layer.

[0252] <Adhesive Sheet with Substrate>

[0253] When the adhesive sheet disclosed herein is in the form of an adhesive sheet with a substrate, the thickness of the adhesive sheet may be, for example, less than 1000 μm, less than 600 μm, less than 350 μm, less than 300 μm, or less than 250 μm. From the viewpoint of miniaturization, lightweight, and thinning of products to which the adhesive sheet is applied, in some schemes, the thickness of the adhesive sheet may be, for example, less than 200 μm, less than 175 μm, less than 140 μm, less than 120 μm, or less than 100 μm (for example, less than 100 μm). In addition, from the viewpoint of handleability, the thickness of the adhesive sheet may be, for example, more than 5 μm, more than 10 μm, more than 15 μm, more than 20 μm, more than 25 μm, or more than 30 μm. In some embodiments, the thickness of the adhesive sheet can be, for example, 50 μm or more, 60 μm or more, 80 μm or more, 100 μm or more, 120 μm or more, 150 μm or more, or 200 μm or more. The upper limit of the thickness of the adhesive sheet is not particularly limited.

[0254] It should be noted that the thickness of the adhesive sheet refers to the thickness of the portion that is attached to the adherend. Figure 1 In the PSA sheet 1 having the structure shown, the thickness is the thickness from the PSA surface 21A of the PSA sheet 1 to the second surface 10B of the substrate 10 , and does not include the thickness of the release liner 31 .

[0255] The adhesive sheet disclosed herein can be suitably implemented in a scheme in which, for example, the thickness Ts of the supporting substrate is greater than the thickness Ta of the adhesive layer, that is, in a scheme in which Ts / Ta is greater than 1. Although not particularly limited, Ts / Ta can be, for example, 1.1 or more, 1.2 or more, 1.5 or more, or 1.7 or more. For example, in an adhesive sheet that can be used for the purpose of strengthening, supporting, mitigating impact, etc. of an adherend, due to the increase in Ts / Ta, there is a tendency that a good effect is easily exerted even if the adhesive sheet is thinned. In some schemes, Ts / Ta can be 2 or more (for example, greater than 2), 2.5 or more, or 2.8 or more. In addition, Ts / Ta can be, for example, 50 or less, or 20 or less. From the viewpoint that it is easy to exert a high post-heating adhesive force even if the adhesive sheet is thinned, Ts / Ta can be, for example, 10 or less, 8 or less, or 5 or less.

[0256] The above-mentioned adhesive layer is preferably directly fixed or fixed to the supporting substrate across an elastic intermediate layer. Here, fixation refers to: in the adhesive sheet whose adhesive force is increased after being pasted to the adherend, the adhesive layer is not separated from the supporting substrate to the extent that the adhesive layer is peeled off from the adherend, and the adhesive layer shows sufficient anchoring property (can be anchoring property with the help of an elastic intermediate layer) to the supporting substrate. According to the adhesive sheet with a substrate fixed to the supporting substrate by the adhesive layer, the adherend and the supporting substrate can be firmly integrated. As a preferred example of an adhesive sheet in which the adhesive layer is fixed to the substrate, it can be listed: when measuring the above-mentioned heating post-adhesive force, an adhesive sheet in which no peeling (anchoring failure) occurs between the adhesive layer and the supporting substrate. An adhesive sheet in which the heating post-adhesive force is more than 10N / 20mm and anchoring failure does not occur when measuring the heating post-adhesive force is a preferred example of an adhesive sheet in which the adhesive layer is fixed to the substrate.

[0257] The adhesive sheet of the form of adhesive layer directly fixed to the supporting substrate is preferably manufactured by the method comprising the following steps in sequence: for example, a liquid adhesive composition is contacted to the first side of the substrate, and the above-mentioned adhesive composition is solidified to form an adhesive layer on the first side. The solidification of the above-mentioned adhesive composition can be accompanied by one or more of the drying, crosslinking, polymerization, cooling, etc. of the adhesive composition. According to the method of forming an adhesive layer by solidifying the liquid adhesive composition on the first side of the substrate, compared with the method of configuring the adhesive layer on the first side by pasting the cured adhesive layer on the first side of the substrate, the anchoring property of the adhesive layer for the substrate can be improved. It can be utilized to suitably manufacture the adhesive sheet in which the adhesive layer is fixed on the substrate.

[0258] In some schemes, as a method for contacting the first surface of the substrate with the liquid adhesive composition, a method of directly applying the above-mentioned adhesive composition to the first surface of the substrate can be adopted. By making the first surface (adhesive surface) of the adhesive layer cured on the first surface of the substrate abut against the release surface, it is possible to obtain an adhesive sheet in which the second surface of the adhesive layer is fixed to the first surface of the substrate, and the first surface of the adhesive layer abuts against the release surface. As the above-mentioned release surface, the surface of the release liner, the back of the substrate after release treatment, etc. can be used.

[0259] In addition, in the case of a photocurable adhesive composition using a partial polymer (polymer slurry) of a monomer raw material, for example, the adhesive layer can also be formed in the following manner: after applying the adhesive composition to the release surface, the first surface of the substrate is covered on the applied adhesive composition so that the first surface of the substrate contacts the above-mentioned uncured adhesive composition, and in this state, the adhesive composition sandwiched between the first surface of the substrate and the release surface is irradiated with light to cure it, thereby forming.

[0260] It should be noted that the above-mentioned exemplified method is not intended to limit the manufacturing method of the adhesive sheet disclosed herein. When manufacturing the adhesive sheet disclosed herein, one or more suitable methods capable of fixing the adhesive layer to the first surface of the substrate can be used alone or in combination. As described above, examples of this method include the following methods: a method of curing a liquid adhesive composition on the first surface of the substrate to form an adhesive layer; a method of applying a surface treatment to the first surface of the substrate to improve the anchoring property of the adhesive layer; a method of providing a primer on the first surface of the substrate; a method of sandwiching an elastic intermediate layer between the first surface of the substrate and the adhesive layer, etc. For example, an adhesive sheet can be manufactured by the following method: a method of pasting a cured adhesive layer on the first surface of a substrate to which a surface treatment for improving anchoring property has been applied; a method of pasting a cured adhesive layer on an elastic intermediate layer provided on the first surface of the substrate, etc. In addition, the anchoring property of the adhesive layer to the substrate can also be improved by selecting the material of the substrate and the composition of the adhesive. In addition, by applying a temperature higher than room temperature to an adhesive sheet having an adhesive layer on the first surface of the substrate, the anchoring property of the adhesive layer to the substrate can be improved. The temperature used to improve the anchoring property can be selected from a temperature lower than the expansion starting temperature T1 of the heat-expandable microspheres (preferably a temperature lower by 5°C or more, more preferably a temperature lower by 10°C or more), and can be, for example, about 35°C to 80°C, about 40°C to 70°C, or about 45°C to 60°C.

[0261] The adhesive sheet disclosed herein is an adhesive sheet (i.e., an adhesive sheet with a substrate having two-sided adhesiveness) in the form of a first adhesive layer arranged on the first side of a substrate and a second adhesive layer arranged on the second side of the substrate, wherein the first adhesive layer and the second adhesive layer can be the same composition or different compositions. When the composition of the first adhesive layer and the second adhesive layer is different, the difference can be, for example, the difference in composition, the difference in structure (thickness, surface roughness, formation range, pattern formation, etc.). For example, the second adhesive layer can be a layer without the function of being easily peeled off again, or can be, for example, an adhesive layer without heat-expandable microspheres. In addition, the surface (second adhesive surface) of the second adhesive layer can be a face that does not deliberately take into account the initial low adhesiveness and the strong adhesiveness during use.

[0262] <Adhesive Sheet with Release Liner>

[0263] The adhesive sheet disclosed herein can present the form of an adhesive product obtained by making the surface (adhesive surface) of the adhesive layer abut against the release surface of the release liner. Therefore, according to this specification, an adhesive sheet with a release liner (adhesive product) comprising any adhesive sheet disclosed herein and a release liner having a release surface abutting against the adhesive surface of the adhesive sheet can be provided.

[0264] The thickness of the release liner is not particularly limited, and is usually suitable for about 5 μm to 200 μm. If the thickness of the release liner is within the above range, the workability of sticking to the adhesive layer and the workability of peeling from the adhesive layer are excellent, so it is preferred. In some schemes, the thickness of the release liner can be, for example, more than 10 μm, more than 20 μm, more than 30 μm, or more than 40 μm. In addition, from the viewpoint of easy peeling from the adhesive layer, the thickness of the release liner can be, for example, less than 100 μm, less than 80 μm. The release liner can be subjected to known antistatic treatments such as coating type, mixing type, vapor deposition type, etc. as needed.

[0265] There are no particular limitations on the release liner, and for example, a release liner having a release layer on the surface of a liner substrate such as a resin film, paper (which may be a paper laminated with a resin such as polyethylene) can be used; a release liner comprising a resin film formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. From the perspective of excellent surface smoothness, a release liner having a release layer on the surface of a resin film as a liner substrate, or a release liner comprising a resin film formed of a low-adhesive material can be suitably used. As a resin film, there are no particular limitations as long as it is a film that can protect the adhesive layer, and for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyester film (PET film, PBT film, etc.), polyurethane film, ethylene-vinyl acetate copolymer film, etc. can be cited. For forming the release layer, for example, known release agents such as silicone release agents, long-chain alkyl release agents, olefin release agents, fluorine release agents, fatty acid amide release agents, molybdenum sulfide, and silica powder can be used. In particular, silicone release agents are preferably used.

[0266] The thickness of the release layer is not particularly limited, but is usually about 0.01 μm to 1 μm, preferably about 0.1 μm to 1 μm. The method for forming the release layer is not particularly limited, and a known method can be appropriately adopted depending on the type of release agent used.

[0267] <Purpose>

[0268] The adhesive sheet provided by the specification can exert good reprocessability in the initial stage of, for example, being pasted on the adherend, so it can be helpful to suppress the reduction of yield rate and the high quality of the products containing the adhesive sheet. In addition, the above-mentioned adhesive sheet can greatly improve the bonding force by aging (which can be heating at a temperature lower than the expansion starting temperature T1, over time, their combination, etc.). For example, by heating at a desired time, the adhesive sheet can be firmly bonded to the adherend. And then, the above-mentioned adhesive sheet is heated to a temperature above the expansion starting temperature T1, so that the heat-expandable microspheres can be expanded and the peeling property of peeling off from the adherend can be improved, so that it is easy to peel off from the adherend. Taking full advantage of this feature, the adhesive sheet disclosed herein is heated to a temperature above the expansion starting temperature T1 according to expectations (such as repairing components, recycling components when discarding products, etc.) for the purposes of fixing, joining, molding, decorating, protecting, strengthening, supporting, mitigating impact, etc. of the components contained in various products in various fields, thus can be suitably used as an adhesive sheet that can be easily peeled off from the above-mentioned components. Therefore, the adhesive sheet disclosed herein can be helpful for improving the convenience of product repair, etc., improving the reusability of components included in the product, etc. In addition, the adhesive sheet disclosed herein can have initial reworkability, strong adhesion after the adhesive force increases, and re-peelability achieved by heating to a temperature above the expansion starting temperature T1, and is therefore also useful as a highly reliable temporary fixing means.

[0269] The adhesive sheet disclosed herein can be attached to an adherend in the form of an adhesive sheet with a substrate having an adhesive layer provided on at least the first side of a film-like substrate having a first side and a second side, and suitably used as a reinforcing film to enhance the adherend. In the reinforcing film, as the film substrate, a substrate comprising a resin film as a base film can be suitably used. In addition, from the viewpoint of improving the reinforcing performance, the adhesive layer is preferably fixed to the first side of the film-like substrate.

[0270] For example, in optical components used in optical products and electronic components used in electronic products, high integration, small size, light weight and thinness are being developed, and multiple thin optical components / electronic components with different linear expansion coefficients and thicknesses can be stacked. By pasting the above-mentioned reinforcing film on such components, appropriate rigidity can be given to the above-mentioned optical components / electronic components. As a result, for the manufacturing process and / or the manufactured products, warping and bending caused by stress that may be generated between the above-mentioned multiple components with different linear expansion coefficients and thicknesses can be suppressed.

[0271] Furthermore, in the manufacturing process of optical products / electronic products, when a thin optical component / electronic component is subjected to a shape processing such as cutting processing as described above, by attaching a reinforcing film to the component and treating it, it is possible to alleviate the local stress concentration caused to the optical component / electronic component during the processing, and reduce the risk of cracks, breakage, peeling of the stacked component, etc. Attaching a reinforcing member to the optical component / electronic component and treating it is also beneficial to alleviate the local stress concentration during the transportation, stacking, rotation, etc. of the component, and to suppress the bending or curvature caused by the weight of the component.

[0272] Furthermore, when optical products, electronic products and other devices including the above-mentioned enhancement film are used by consumers in the market, even if the device is dropped, placed under a heavy object, hit by a flying object, etc., and unintentional stress is applied to the device, the device can be relieved by including the enhancement film. Therefore, by including the enhancement film in the above-mentioned device, the durability of the device can be improved.

[0273] In addition, the adhesive sheet disclosed herein can be preferably used in the scheme of being pasted on the components constituting various mobile devices (portable devices). Here, the so-called "portable" is not sufficient to only refer to being able to carry, and it refers to the portability of the level that an individual (standard adult) can carry relatively easily. In addition, the example of the so-called portable device here may include mobile phones, smart phones, tablet computers, notebook computers, various wearable devices, digital cameras, digital video cameras, audio equipment (portable music players, IC recorders, etc.), computers (electronic calculators, etc.), portable game consoles, electronic dictionaries, electronic notepads, e-books, portable electronic devices such as vehicle-mounted information equipment, portable radios, portable televisions, portable printers, portable scanners, portable modems, and mechanical watches, pocket watches, flashlights, small mirrors with handles, etc. The example of the component constituting the above-mentioned portable electronic device can include optical films, display panels, etc. used by image display devices such as thin layer displays, film-type displays, etc. such as liquid crystal displays. The adhesive sheet disclosed herein can be preferably used in the scheme of various components pasted on automobiles, home appliances, etc.

[0274] Example

[0275] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in the specific examples. It should be noted that "parts" and "%" in the following description are based on weight unless otherwise specified.

[0276] <Preparation of Polymer A>

[0277] (Polymer A1)

[0278] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a cooler, 100 parts of n-butyl acrylate (BA), 5 parts of vinyl acetate (VAc), 3 parts of acrylic acid (AA), 0.1 parts of 2-hydroxyethyl acrylate (HEA), 0.3 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator and toluene as a polymerization solvent were added, and the reaction was carried out at 60°C for 6 hours to obtain a solution of polymer A1. The weight average molecular weight (Mw) of polymer A1 is 55×10 4 .

[0279] (Polymer A2)

[0280] Into a reaction vessel equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, 60 parts of 2-ethylhexyl acrylate (2EHA), 15 parts of N-vinyl-2-pyrrolidone (NVP), 10 parts of methyl methacrylate (MMA), 15 parts of HEA, 0.2 parts of AIBN and 200 parts of ethyl acetate as a polymerization solvent were added, and the reaction was carried out at 60° C. for 6 hours to obtain a solution of polymer A2. The Mw of polymer A2 is 110×10 4 .

[0281] (Polymer A3)

[0282] 100 parts of 2EHA, 2 parts of AA, 0.2 parts of AIBN and 200 parts by mass of ethyl acetate as a polymerization solvent were added to a reaction vessel equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, and the reaction was carried out at 60° C. for 6 hours to obtain a solution of polymer A3. The Mw of polymer A3 was 110×10 4 .

[0283] <Preparation of Polymer B>

[0284] (Polymer B1)

[0285] Into a reaction container equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, 60 parts of MMA, 10 parts of n-butyl methacrylate (BMA), 10 parts of 2-ethylhexyl methacrylate (2EHMA), 8.7 parts of a methacrylate monomer containing a polyorganosiloxane skeleton having a functional group equivalent of 900 g / mol (trade name: X-22-174ASX, manufactured by Shin-Etsu Chemical Co., Ltd.), 11.3 parts of a methacrylate monomer containing a polyorganosiloxane skeleton having a functional group equivalent of 4600 g / mol (trade name: KF-2012, manufactured by Shin-Etsu Chemical Co., Ltd.), 100 parts of ethyl acetate and 0.8 parts of α-thioglycerol as a chain transfer agent were added, and after stirring at 70° C. for 1 hour under a nitrogen atmosphere, 0.2 parts of AIBN were added, and after reacting at 70° C. for 2 hours, 0.1 parts by weight of AIBN were added, and then reacted at 80° C. for 5 hours. In this way, a solution of polymer B1 was obtained. The Mw of polymer B1 was 2.0×10 4 .

[0286] (Polymer B2)

[0287] Polymer B2 was prepared in the same manner as polymer B1 except that the composition of the monomer components was changed to 40 parts of MMA, 20 parts of BMA, 20 parts of 2EHMA, 8.7 parts of a methacrylate monomer containing a polyorganosiloxane skeleton with a functional group equivalent of 900 g / mol (X-22-174ASX), and 11.3 parts of a methacrylate monomer containing a polyorganosiloxane skeleton with a functional group equivalent of 4600 g / mol (KF-2012). The Mw of polymer B2 was 2.2×10 4 .

[0288] The weight average molecular weight of each of the above polymers was measured using a GPC apparatus (HLC-8220GPC manufactured by Tosoh Corporation) under the following conditions and was determined in terms of polystyrene.

[0289] [GPC conditions]

[0290] Sample concentration: 0.2wt% (tetrahydrofuran (THF) solution)

[0291] Sample injection volume: 10μL

[0292] Eluent: THF

[0293] Flow rate: 0.6mL / min

[0294] ·Measurement temperature: 40℃

[0295] ·column:

[0296] Sample column: TSK guardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns)

[0297] Reference column: TSKgel SuperH-RC (1 column)

[0298] Detector: Differential Refractometer (RI)

[0299] <Production of elastic middle layer>

[0300] (Elastic middle layer F1)

[0301] To the solution of polymer A1, 40 parts of a tackifier resin and 2 parts of an isocyanate crosslinking agent X1 (manufactured by Tosoh Corporation, trade name "CORONATE L", a 75% ethyl acetate solution of a trimethylolpropane / toluene diisocyanate trimer adduct) were added relative to 100 parts of the acrylic polymer contained in the solution, and the mixture was stirred and mixed to prepare an adhesive composition f1 for forming an elastic intermediate layer. As the above-mentioned tackifier resin, 10 parts of polymerized rosin ester having a softening point of about 125°C (trade name "HARITAC PCJ", manufactured by HARIMA CHEMICALS INC.), 10 parts of stabilized rosin ester having a softening point of about 80°C (trade name "HARITAC SE10", manufactured by HARIMA CHEMICALS INC.), 5 parts of hydrogenated rosin methyl ester (trade name "M-HDR", manufactured by Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd., liquid) and 15 parts of terpene phenolic resin having a softening point of about 133°C (trade name "SUMILITERESIN PR-12603", manufactured by Sumitomo Bakelite Co., Ltd.) were used.

[0302] Prepare two polyester release films with one side being a release surface formed by a silicone release agent. Apply the above-mentioned adhesive composition f1 on the release surface of these release films, dry it and form an adhesive layer of the same thickness on each release film. Paste these adhesive layers on a non-woven fabric with a thickness of 75 μm (a non-woven fabric obtained by mixing 1% vinylon with 99% Manila hemp. The density is 0.30 g / cm 3 ) on the first and second surfaces of the nonwoven fabric, a double-sided adhesive sheet with a substrate having an adhesive layer with a total thickness of 160 μm was prepared. This double-sided adhesive sheet was used as the elastic intermediate layer F1.

[0303] (Elastic middle layer F2)

[0304] To the polymer A2 solution, 2.5 parts of an isocyanate crosslinking agent X2 (trade name: TAKENATE D110N, trimethylolpropane xylylene diisocyanate, manufactured by Mitsui Chemicals, Inc.) was added based on 100 parts of the acrylic polymer contained in the solution, and the mixture was stirred and mixed to prepare an adhesive composition f2 for forming an elastic intermediate layer.

[0305] The adhesive composition f2 was applied to the release surface of a polyester release film having a release surface formed on one side with a silicone-based release agent and dried to prepare a double-sided adhesive sheet without a substrate having a thickness of 30 μm. This double-sided adhesive sheet without a substrate was used as the elastic intermediate layer F2.

[0306] <Preparation of Adhesive Sheet>

[0307] (Example 1)

[0308] In the solution of polymer A1, 5 parts of polymer B1, 5 parts of isocyanate crosslinking agent X1 (CORONATE L) based on the solid content, and 100 parts of heat-expandable microspheres C1 (manufactured by Matsumoto Oil Pharmaceutical Co., Ltd., trade name "Matsumoto Microsphere F-501D", expansion starting temperature of 120°C, average particle size of 10 μm) were added to 100 parts of polymer A1 contained in the solution, and the mixture was uniformly mixed to prepare an adhesive composition D1.

[0309] The adhesive composition D1 was applied to the release surface of a release liner R1 (MRQ25T100 manufactured by Mitsubishi Chemical Corporation, thickness 25 μm) having a release surface formed by a silicone release agent on one side of a polyester film and dried at 70° C. for 5 minutes to form a heat-expandable adhesive layer E1 having a thickness of 40 μm.

[0310] One adhesive surface of the elastic intermediate layer F1 was attached to the first surface of a polyethylene terephthalate (PET) film (manufactured by Toray Industries, Inc., trade name "Lumirror") having a thickness of 50 μm as a supporting substrate. Next, the heat-expandable adhesive layer E1 was attached to the other adhesive surface of the elastic intermediate layer F1. In this way, the adhesive sheet with a release liner was obtained in the form of an adhesive sheet as described in Example 1 in which the adhesive surface thereof was in contact with the release surface of the release liner R1.

[0311] (Example 2)

[0312] In the solution of polymer A1, 5 parts of polymer B2, 5 parts of isocyanate crosslinking agent X1 (CORONATE L) based on the solid content, and 100 parts of heat-expandable microspheres C2 (manufactured by Matsumoto Oil Pharmaceutical Co., Ltd., trade name "Matsumoto Microsphere F-100VSD", expansion starting temperature of 170°C, average particle size of 10 μm) were added to 100 parts of polymer A1 contained in the solution, and the mixture was uniformly mixed to prepare an adhesive composition D2.

[0313] A PSA sheet described in Example 2 was prepared in the same manner as in Example 1 except that PSA composition D2 was used instead of PSA composition D1.

[0314] (Example 3)

[0315] In the solution of polymer A2, 2.5 parts of polymer B2, 2.5 parts of isocyanate crosslinking agent X2 (TAKENATE D110N) based on solid content, and 50 parts of heat-expandable microspheres C1 (Matsumoto Microsphere F-501D) were added to 100 parts of polymer A2 contained in the solution, and the mixture was evenly mixed to prepare an adhesive composition D3.

[0316] A PSA sheet described in Example 3 was prepared in the same manner as in Example 1 except that PSA composition D3 was used instead of PSA composition D1.

[0317] (Example 4)

[0318] In the solution of polymer A3, 2.5 parts of polymer B1, 2 parts of isocyanate crosslinking agent X1 (CORONATE L) based on the solid content, and 30 parts of heat-expandable microspheres C3 (manufactured by Matsumoto Oil Pharmaceutical Co., Ltd., trade name "Matsumoto Microsphere F-301SD", expansion starting temperature of 90°C, average particle size of 15 μm) were added to 100 parts of polymer A3 contained in the solution, and uniformly mixed to prepare adhesive composition D4.

[0319] A PSA sheet described in Example 4 was prepared in the same manner as in Example 1 except that PSA composition D4 was used instead of PSA composition D1 and elastic intermediate layer F2 was used instead of elastic intermediate layer F1.

[0320] <Measurement and Evaluation>

[0321] (Storage modulus G'(T1))

[0322] The storage modulus G'(T1) of the polymer A1 contained in the adhesive layer of the adhesive sheet described in Example 1 is obtained by dynamic viscoelasticity measurement. Specifically, the adhesive composition is applied to the release surface of the release liner instead of the PET film, and the adhesive layer is formed under substantially the same conditions as in Example 1, and multiple adhesive layers are repeated to form an adhesive layer with a thickness of about 2 mm. The adhesive layer is punched into a disc with a diameter of 7.9 mm, and the test sample thus prepared is clamped and fixed with parallel plates, and a dynamic viscoelasticity measurement is performed under the following conditions using a viscoelasticity tester ("ARES" manufactured by TA Instruments Co., Ltd.), and the storage modulus G' at the expansion starting temperature T1 (i.e., 120°C) of the heat-expandable microsphere C1 is obtained.

[0323] ·Measurement mode: Shear mode

[0324] Temperature range: -50℃~200℃

[0325] Heating rate: 5℃ / min

[0326] ·Measurement frequency: 1Hz

[0327] Similarly, for the polymer A contained in the adhesive layer described in Examples 2 to 4, the storage modulus G' at the expansion starting temperature T1 of the heat-expandable microspheres contained in the adhesive layer was determined.

[0328] (Measurement of Adhesion Strength N1)

[0329] The pressure-sensitive adhesive sheet described in each example was cut into a 20 mm width together with a release liner to prepare a test piece.

[0330] Under the standard environment of 23 ℃ and 50% RH, peel off the release liner covering the adhesive surface of the test piece, and press the exposed adhesive surface back and forth once on the stainless steel plate (SUS304 BA plate) as the adherend with a 2kg roller. After placing it under the above-mentioned standard environment for 30 minutes, use a universal tensile compression tester (device name "tensile compression tester, TCM-1kNB", MINEBEAMITSUMI INC. system) to measure the 180° peeling adhesion (resistance to the above-mentioned stretching) under the conditions of 180 degrees of peeling angle and 300mm / minute of tensile speed according to JIS Z0237. The measurement was carried out 3 times, and their average value is shown in Table 1 as the initial adhesion (N1) [N / 20mm].

[0331] (Measurement of Adhesion Strength N2)

[0332] The test piece that will be pressed on adherend in the same operation as the mensuration of above-mentioned adhesive force N1 is heated 5 minutes under the temperature (heat treatment temperature T2) of 20 ℃ lower expansion starting temperature T1 of the heat-expandable microsphere contained in the adhesive layer of this test piece, then, after being placed 30 minutes under above-mentioned standard environment, 180 ° peeling adhesive force is measured in the same manner. Measure and carry out 3 times, and their mean value is shown in Table 1 as adhesive force (N2) [N / 20mm] after heating.

[0333] (Evaluation of peelability at expansion starting temperature T1)

[0334] The test piece pressed onto the adherend in the same manner as the determination of the above-mentioned adhesive force N1 was heated at the heating treatment temperature T2 for 5 minutes, and then placed under the above-mentioned standard environment for 30 minutes. Then, it was heated at the expansion starting temperature T1 for 5 minutes, and after being placed under the above-mentioned standard environment for 30 minutes, the 180° peeling adhesive force was measured in the same manner. The measurement was performed 3 times, and their average value was taken as the adhesive force after expansion treatment (N3). Based on the results obtained, the peelability was evaluated using the following 3 levels. The results are shown in Table 1. It should be noted that the adhesive sheets of Examples 1 to 3 were peeled off and floated from the adherend from both sides of the width direction of the test piece to near the center of the width by heating at the expansion starting temperature T1 for 5 minutes, and the test piece was extremely easy to peel off from the above-mentioned adherend.

[0335] E: Adhesion after expansion treatment is less than 0.5N / 20mm (excellent peelability)

[0336] G: Adhesion after expansion treatment is 0.5 N / 20 mm or more and less than 1.0 N / 20 mm (good peelability)

[0337] P: Adhesion after expansion treatment is 1.0N / 20mm or more (lack of peelability)

[0338] [Table 1]

[0339] Table 1

[0340]

[0341] As shown in Table 1, the adhesive strength increase ratio (N2 / N1) of the adhesive sheets described in Examples 1 to 3 is 3.0 or more, and the initial adhesive strength is greatly increased by heating for 5 minutes at a temperature sufficiently lower than the expansion starting temperature T1 (heating treatment temperature T2). In addition, after the adhesive strength of the adhesive sheets of Examples 1 to 3 is increased by heating at the heating treatment temperature T2, they can be easily peeled from the adherend by heating at the expansion starting temperature T1.

[0342] In summary, although the specific examples of the present invention have been described in detail, these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.

Claims

1. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer, The adhesive layer comprises a polymer A as a base polymer and heat-expandable microspheres having an expansion starting temperature T1, The adhesive layer further comprises a polymer B, The polymer B is a copolymer of a monomer having a polyorganosiloxane skeleton and a (meth)acrylic monomer. The glass transition temperature Tg of the polymer B calculated based on the composition of the (meth)acrylic monomer using the Fox equation is: B 30°C or higher and 120°C or lower, The glass transition temperature Tg B 20°C or more lower than the expansion starting temperature T1, The adhesive force N2 of the PSA sheet measured at 23°C after being bonded to a stainless steel plate and heated at a temperature 20°C lower than the expansion starting temperature T1 for 5 minutes is 3.0 times or more of the adhesive force N1 measured after being bonded to a stainless steel plate and kept at 23°C for 30 minutes.

2. The adhesive sheet according to claim 1, wherein The storage modulus G' of the polymer A at the expansion starting temperature T1 is 1×10 4 Pa~1×10 6 Pa.

3. The adhesive sheet according to claim 1 or 2, wherein The glass transition temperature Tg calculated by the Fox equation based on the composition of the monomer components constituting the polymer A is: A It is -65°C or higher and lower than 0°C.

4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The adhesive layer contains 10 parts by weight or more and 200 parts by weight or less of the heat-expandable microspheres based on 100 parts by weight of the polymer A.

5. The pressure-sensitive adhesive sheet according to any one of claims 1 to 4, wherein The content of the polymer B in the adhesive layer is 0.5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the polymer A. 6 . The pressure-sensitive adhesive sheet according to claim 1 , comprising a supporting substrate having a first surface and a second surface, wherein the pressure-sensitive adhesive layer is laminated on at least the first surface of the supporting substrate.

7. The adhesive sheet according to claim 6, wherein An elastic intermediate layer is disposed between the adhesive layer and the first surface of the supporting substrate.